Stable isotope signatures for interpreting metal accumulation in bulk zooplankton across a nearshore–offshore gradient on the southwestern coast of Taiwan - Mark Ariel D. Malto; Yee Cheng Lim; Chih-Feng Chen; Frank Paolo Jay B. Albarico; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

Overflow metabolism drives high-rate carbon, nitrogen and phosphorus sequestration in an enriched aerobic microbial community - Dilani D. Jayathilaka; Md Iqbal Hossain; Linda L. Blackall; Ka Yu Cheng; Ranjan Sarukkalige; Maneesha P. Ginige (Water Research, 2026)

Algal-bacterial symbiosis enhances adaptation to nutrient limitation under low light in urban water: Transcriptomic insights into chloroplast-centered metabolic reprogramming - Juan Zhang; Chen Zhou; Xiyan Ji; Rudy D’Alessandro; Shoutao Cheng (Bioresource Technology, 2026)

Enhancement by Ce addition to La-Zr-mixed oxide supported Ni catalysts on the mid-temperature steam reforming of methane - Li-Chun Lin; Teng-Li Yu; Cheng-Yao Hung; Guan-Yu Chen; Yi-Ning Chao; Shawn D. Lin (Fuel, 2026)

Overlooked properties difference of biogenic sulfur resulting in distinct performance in serving as an electron donor for microbial denitrification - N. Zhang; G. Yi; R. Ren; G. Zhang; D. Ren; X. Ba; H. Xu; H.-Y. Cheng (Water Research, 2026)

Electronic structure engineering of 2D Ni-MOF/CNTs for glucose monitoring and energy supply in a wearable sweat sensor system - Rui-Dong Shi; Guo-Tao Xiang; Tao Cheng; Zi-Dong Zhou; Na Chen; Raul D. Rodriguez; Jin-Ju Chen (Chemical Engineering Journal, 2026)

Sedimentary records of silicate weathering on the continental shelf of the South Yellow Sea during glacial periods - Jin Zhang; Shiming Wan; Yifei Yang; Shouye Yang; Peter D. Clift; Yulong Guo; Debo Zhao; Yi Tang; Zhaojie Yu; Zehua Song; Zhongjing Cheng; Zaibao Yang; et al. (Science China Earth Sciences, 2026)

Temperature-controlled and topographically shaped depth gradient succession of siliceous radiolarians and their connectivity across the Eauripik Rise - Xiawen Cheng; Tong Li; Lanlan Zhang; Zhanlin Liang; B. G. D. Ojithma Perera; Ranfei Sun; Yan Du (Science China Earth Sciences, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Effect of the protein content and amount of native whey protein on properties of heat and acid-induced milk gels - Zhe Cheng; Pauline van Leusden; Matthias D. Eisner; Lilia Ahrné (International Dairy Journal, 2026)

Organic pollutants and phytoplankton dynamics across contrasting coastal environments - Aiza D. Gabriel; Yee Cheng Lim; Chih-Feng Chen; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

Intensification of distillation processes using column stacking facilitated by heat pumps for energy recovery - Hsiao-Te Liu; Ting-Cheng Lee; Jeffrey D. Ward (Process Safety and Environmental Protection, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Late Cretaceous cerium anomalies and globally distinctive redox responses before, during and after Oceanic Anoxic Event 2 - Cheng Cao; Xiao-Ming Liu; Jeremy D. Owens; Hugh C. Jenkyns (Geochimica et Cosmochimica Acta, 2026)

Microplastic pollution and thermal increase alter cellular stress responses and microbiomes in Antarctic and sub-Antarctic fish - Daniela Nualart C; Guillaume Schwob; Julieta Orlando; Kurt Paschke; Pedro M. Guerreiro; Stephen D. McCormick; Chi-Hing Christina Cheng; Luis Vargas-Chacoff (Environmental Pollution, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Mechanisms and environmental factors of mercury methylation in wetlands: a systematic review - Y. Wang; Y. Liu; H. Cai; D. Zheng; Q. Cheng (International Journal of Energy and Water Resources, 2026)

Neuroimaging as the ‘missing link’ for preclinical to clinical translation: an example using N-acetylcysteine among individuals with cocaine- and opioid-use disorders receiving methadone treatment - Spencer Birney; Annie Cheng; Theresa Babuscio; Stephanie Dwy; Skye Orazietti; Patrick D. Worhunsky; Julia Shi; Mehmet Sofuoglu; Todd Constable; Marc N. Potenza; Kathleen Carroll; Sarah W. Yip (Psychopharmacology, 2026)

Climatology and annual cycle of global ocean dissolved oxygen represented by multiple observational gridded products - Juan Du; Lijing Cheng; Takamitsu Ito; Hernan E. Garcia; Zhankun Wang; Jonathan D. Sharp; Christopher J. Roach; Shoshiro Minobe; Yuntao Zhou; Bin Lu; Gian Giacomo Navarra; Seth M. Bushinsky (Ocean Science, 2026)
Ocean dissolved oxygen (O2) is an essential climate variable crucial for sustaining the marine life; thus, changes of O2 at various spatiotemporal scales should be quantified and understood. Here, we study the climatology and annual cycle of O2 at regional to global scales using eight available gridded observational products. These datasets are generated by different groups using different primary data selection, quality control, bias correction, and interpolation methods, including statistical and machine-learning-based mapping methods. A common set of metrics was collaboratively developed by the community of the Gridded Observational Dataset Intercomparison Project-Dissolved Oxygen (GODIP-DO) to facilitate the inter-comparison. We find that global mean O2 profiles are consistent among all products (±3 µmol kg−1), with the well-established decrease from high surface values to a minimum ∼ 1000 m, and subsequent increase to higher O2 at depth, although local differences could reach ±25 µmol kg−1 (0–1000 m). The hemispheric O2 annual cycle correlates strongly with ocean temperature changes, suggesting the key driver of temperature for the O2 annual cycle. However, there is substantial variation in the global mean 0–100 m O2 annual cycle, the magnitude ranges from −1 to 0.8 µmol kg−1, with a standard deviation of the datasets of ∼ 0.3 µmol kg−1. Average oxygen minimum zones (OMZ) volume among the products is 80.92 × 106 km3 (±1.95 %) for a 60 µmol kg−1 threshold and 152.00 × 106 km3 (±1.72 %) for a 90 µmol kg−1 threshold. Our results help to depict and understand the spread among the available O2 gridded datasets.

Microplastic disparities between urban (Buru-un) and rural (Tubajon) seagrass beds of Northern Mindanao, Philippines - Aiza D. Gabriel; Yee Cheng Lim; Frank Paolo Jay B. Albarico; Joanna Mea Celmar; Chiu-Wen Chen; Cheng-Di Dong; Hernando P. Bacosa (Journal of Soils and Sediments, 2026)

The evolution of the cave's entrance of Bruniquel and consequences for its accessibility by early Homo neanderthalensis - K. Génuite; S. Verheyden; H. Camus; C. Burlet; M. Boudadi-Maligne; L. Bruxelles; H. Cheng; D. Cochard; S. Delaby; E. Fabre; C. Ferrier; C. Lézin; et al. (Quaternary Science Reviews, 2026)

Data fusion for fine-scale ozone mapping in the New York City metropolitan area using low-cost sensors and model information - Ellie Hojeily; Cheng-Hsuan Lu; Stefano Alessandrini; Ju-Hye Kim; Rajesh Kumar; Shih-Wei Wei; Liam Sheji; Md. Aynul Bari; Scott D. Miller (Atmospheric Environment, 2026)

Changes in Body Size With Age Do Not Follow the Temperature‐Size Rule - Jennifer S. Bigman; Lewis A. K. Barnett; James T. Thorson; Sean C. Anderson; Krista B. Oke; Kelly A. Kearney; Darren J. Pilcher; Wei Cheng; Esther D. Goldstein; Mary E. Matta; Kirstin K. Holsman; Lauren A. Rogers (Global Ecology and Biogeography, 2026)
Aim The temperature‐size rule is often described as a reduction in ectothermic asymptotic or maximum body size with warming. Although this coincides with the expectation that faster growth under warming would lead to larger sizes early in life but smaller sizes later in life, there remain few tests of changes in size across ontogeny. Here, we use > 99,000 observations of weight‐at‐age of commercially important fishes over 25 years to ask whether changes in size across ontogeny can be explained by temperature. We also examine whether oxygen, a key part of a proposed mechanism behind the temperature‐size rule, explains patterns of weight‐at‐age better than temperature. Understanding how temperature and oxygen affect size across age offers a test of macroecological theory and can inform the future productivity of fisheries. Location Bering Sea, largest subarctic system (Latitude: 52° N–66° N, Longitude: 160° E–170° W). Time Period 1987–2023. Major Taxa Studied Commercially important fishes. Methods We coupled fisheries‐independent survey data and climate model output with spatiotemporal generalised linear mixed‐effects models, a novel framework for testing the temperature‐size rule. These models account for uneven sampling across space and time to assess long‐term trends, as well as the effects of temperature and oxygen on size across age. We additionally explore the effect of model structure on our results by comparing functional forms and how spatial and/or spatiotemporal random effects are included. Results Weight‐at‐age was variable over time for all species with no long‐term trend. Temperature better explained this variability than oxygen, but effects were small and not age‐specific, counter to the temperature‐size rule. Our results were sensitive to model structure as models with shared spatial effects across ages appeared to support temperature‐size rule predictions, but this support reflected spatial autocorrelation in size rather than age‐specific temperature responses. Collectively, this work shows that support for the temperature‐size rule in these fishes was an artifact of spatial patterns in size and growth. Main Conclusions Our work tests macroecological theory using nearly complete body size trajectories to understand not only changes in adult stages but how size changes across age. We highlight that relationships among size, growth, temperature, and oxygen are not as straightforward as theory suggests and illustrate that modelling decisions can have a large effect on tests of ecological theory, and more broadly, our ability to understand biological responses to climate change.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

Thermal valorization of marine-derived wastes: A critical review on coupled mechanisms of metal stabilization and organic pollutant degradation - Kent Naiah D. Araña; Yee Cheng Lim; Chiu-Wen Chen; Cheng-Di Dong (Journal of Hazardous Materials, 2026)

Identifying green leaf and leaf phenology of large trees and forests by time series PlanetScope and Sentinel-2 images and the chlorophyll and green leaf indicator (CGLI) - Baihong Pan; Xiangming Xiao; Li Pan; Andrew D Richardson; Yujie Liu; Yuan Yao; Cheng Meng; Yanhua Xie; Chenchen Zhang; Yuanwei Qin (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Trace metal and rare-earth element concentrations and distribution in freshwater-estuarine karst subterranean river benthic organisms, the Philippines - Frank Paolo Jay B. Albarico; Genese Divine B. Cayabo; Rodulf Anthony T. Balisco; Ming-Huang Wang; Mark Ariel D. Malto; Wen-Chien Huang; Te-Yu Liao; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Toward sustained and efficient n-caproate production: Insights into magnetite-encapsulated biochar mediated microbial chain elongation - Benteng Wu; Yangjuan Cheng; Jing Gu; Haoran Yuan; Jerry D. Murphy (Bioresource Technology, 2026)

Identifying Headwater Streams across the Conterminous United States - Charles R. Lane; Ellen D’Amico; Jay R. Christensen; Heather E. Golden; Frederick Y. Cheng; John C. Hammond; Admin Husic; Kristin L. Jaeger; C. Nathan Jones; Christa A. Kelleher; Li Li; D. Tyler Mahoney; et al. (Ecosystems, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Spatial and temporal variations in the distribution of eastern Australian post-orogenic granites and related mineral deposits: metallogenic and tectonic significance - D. L. Huston; Y. Cheng; S. L. Jones; D. C. Champion; M. D. Norman; M. W. Agnew; A. Cross; V. C. Bennett; R. A. Creaser (Australian Journal of Earth Sciences, 2026)

Abiogenic particulate and plankton size affecting polycyclic aromatic hydrocarbons in coastal plankton - Aiza D. Gabriel; Yee Cheng Lim; Frank Paolo Jay B. Albarico; Mark Ariel D. Malto; Chih-Feng Chen; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

Spatial distribution, sources, and biomagnification of PAHs, PAEs, and APs in phytoplankton and zooplankton from Kaohsiung Harbor - Mark Ariel D. Malto; Yee Cheng Lim; Frank Paolo Jay B. Albarico; Chih-Feng Chen; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Intestinal acinar adenocarcinoma in a blue-fronted Amazon parrot (Amazona aestiva) - João C. Krueger; Carolina Fontana; Arthur C. Cheng; Vinicius Dahm; Rachel Teixeira Neto; Luana Canavessi; Nelson D. Lucas; Luana C. Stunitz da Silva; Anderson Luiz de Carvalho; Aline de Marco Viott; Manoela M. Piva (Journal of Comparative Pathology, 2026)

Effect of milk pH during heating on gelation and textural properties of heat and acid-induced milk gels - Zhe Cheng; Pauline van Leusden; Matthias D. Eisner; Lilia Ahrné (International Dairy Journal, 2026)

Water optimization of ground cover rice production system to synergistically achieve carbon and nitrogen emissions reduction—based on environmental footprints of different precipitation year types - Jian Ren; Cheng Hu; William D. Batchelor; Kelin Hu; Hong Wang; Haitao Liu; Shihua Lü (Agricultural Systems, 2026)

A new Myxospora ( Hypocreales, Sordariomycetes ) species from the Tibetan Plateau, China - Shu-Cheng He; Vinodhini Thiyagaraja; Chitrabhanu S. Bhunjun; Ruvishika S. Jayawardena; Putarak Chomnunti; F. Al-Otibi; Yun-Wei Zhao; Qi Zhao; Kevin D. Hyde (New Zealand Journal of Botany, 2025)

Biochar promoted soil organic carbon accumulation and aggregate stability by increasing the content of organic complex metal oxides in paddy soil - Jiajun Wu; Bin Zhou; Zichuan Li; Cheng Liu; Yan Li; Yulin Wang; Ning Zhao; Zhuozhe Wang; Yanjun Chai; Antonio Scopa; Marios Drosos; Vishnu D. Rajput; et al. (Soil and Tillage Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Revealing the hidden environmental risks: A two-step sequential extraction of mobile and immobile (mineral-bound) microplastics in coral reef sediments - Noralyn G. Dimaongon; Kent Naiah D. Araña; Chiu-Wen Chen; Chih-Feng Chen; Cheng-Di Dong; Chien-Er Huang (Environmental Research, 2025)

Assessing microbial fuel cell performance through integrated rotational dynamics in simulated microgravity - Chin-Tsan Wang; K. Vasumathi; D. Dhanalakshmi; Manas Jaiswal; Jer-Huan Jang; Cheng-Ying Chung (Chemical Engineering Journal, 2025)

Two novel species of Hermatomyces (Dothideomycetes) from Fagales in China - Yan-Yan Yang; Tai-Shun Li; Chitrabhanu S. Bhunjun; Vinodhini Thiyagaraja; Darbhe J. Bhat; Shu-Cheng He; Qi Zhao; Fatimah Al-Otibi; Pattana Kakumyan; Kevin D. Hyde (Mycological Progress, 2025)

Combined effects of PVC microplastics and thermal rise alter the oxidative stress response in Antarctic fish Harpagifer antarcticus and Sub-Antarctic Harpagifer bispinis - Daniela P. Nualart; Kurt Paschke; Pedro M. Guerreiro; Stephen D. McCormick; Claudio González-Wevar; Chi-Hing Christina Cheng; Luis Vargas Chacoff (Marine Pollution Bulletin, 2025)

Hydrological variability in the Black Sea region during the last 670,000 years recorded in multi-proxy speleothem records from northern Türkiye - F. Held; H. Cheng; R.L. Edwards; T. Kipfer; O. Tüysüz; K. Koç; S. Affolter; D. Fleitmann (Quaternary Science Reviews, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Equilibrium carbon, magnesium and position-specific oxygen isotope fractionations in the magnesium carbonate – water – carbon dioxide system based on quantum mechanical calculations and laboratory precipitation experiments - Surjyendu Bhattacharjee; Avni S. Patel; Jie Cheng; Maija J. Raudsepp; Sasha Wilson; William A. Goddard; Paul D. Asimow; John M. Eiler (Geochimica et Cosmochimica Acta, 2025)

Chronic effects of wildfire smoke and criteria air pollutants on cardiovascular hospitalization rates in the contiguous US - Cheng Jin; Mahdieh Danesh Yazdi; Hanbing He; Edgar Castro; Joel D. Schwartz; Robert O. Wright; Yaguang Wei (Environmental Research, 2025)

Will assimilating VIIRS AOD data improve New Delhi's air pollution forecasts as much as assimilating MODIS AOD? - Rajesh Kumar; Scott Meech; Prafull P. Yadav; William Y.Y. Cheng; Sachin D. Ghude; Stefano Alessandrini; Rajmal Jat; Gaurav Govardhan (Atmospheric Environment, 2025)

Study on the change of multi-season urban heat island effect from the perspective of urban functional zones - T. Su; X. S. Dou; X. Y. Cui; D. Liu; B. Lei; M. N. Yuan; R. J. Chen; X. Cheng (International Journal of Environmental Science and Technology, 2025)

Meso- and microplastics accumulation and ecological risks in Philippine urban and rural sandy beaches - Zy D. Perpetua; Frank Paolo Jay B. Albarico; Rey Y. Capangpangan; Ruei-Feng Shiu; Yee Cheng Lim; Chiu-Wen Chen; Cheng-Di Dong; Hernando P. Bacosa (Estuarine, Coastal and Shelf Science, 2025)

Immunomodulatory properties of an arabinan polysaccharide extracted from Sida cordifolia: isolation, characterization and in vitro mechanism of action - Fang Cheng; Xiaobei Pan; Anna Notaro; Andrea Iovine; Antonio Molinaro; Cristina De Castro; Brian D. Green (Carbohydrate Polymers, 2025)

Ice crystal structure melting: insights from molecular dynamics simulations - Ran Wang; Shaohong Cheng; David S.-K. Ting; Arash Raeesi; Sean McTavish; Annick D'Auteuil (Cold Regions Science and Technology, 2025)

A data-driven index for evaluating BMP water quality performance - Elizabeth A. Fassman-Beck; Edward D. Tiernan; Ka Lun Cheng; Kenneth C. Schiff (Water Research, 2025)

Valorization of contaminated dredged harbor sediments into artificial aggregates: Metal immobilization, environmental safety, and carbon footprint - Kent Naiah D. Araña; Yee Cheng Lim; Chih-Feng Chen; Frank Paolo Jay B. Albarico; Noralyn G. Dimaongon; Chiu-Wen Chen; Cheng-Di Dong (Waste Management, 2025)

Assessing playgrounds ultraviolet radiation (UVR) environments in College Station, Texas: Creating UVR-safe environments for children - Wenwen Cheng; Robert D. Brown; Galen Newman (Environmental Research, 2025)

Proofreading of mismatches within primer-template junctions by Escherichia coli DNA polymerase I in vitro and in vivo - Hui-Lan Chang; Kang-Yi Su; Steven D. Goodman; Yung-Chu Chuang; Shen-Jyue Hsu; Yi-Kai Fang; Hsiao-Pei Yu; Cheng-Hao Fang; Ya-Chien Yang; Sui-Yuan Chang; Woei-horng Fang (DNA Repair, 2025)

Approaches to enhancing grain yield and carbon neutrality with organic and inorganic fertilizer practice in Chinese paddy fields - Xiafei Li; Zhenglan Peng; Tao Liu; Bo Cheng; Xinrui Li; William D. Batchelor; Zongkui Chen (Food Security, 2025)

Green, Sustainable, and Melt-Compoundable PLA Composites Reinforced with Spray-Dried Lignocellulosic Nanofibrils for Enhanced Barrier and Mechanical Properties - To Yu Troy Su; Rafaela Aguiar; Nello D. Sansone; Cheng Hao; Ning Yan; Patrick C. Lee (Chemical Engineering Journal, 2025)

Fast arc retreat in the eastern Mediterranean: constraints from late Campanian forearc deposits (Donousa, Greece) - S. O. Martha; P. Xypolias; C. Cheng; W. Dörr; A. Gerdes; D. C. Hezel; M. Kutzschbach; L. Millonig; H. Schmeling; H. R. Marschall; W. Müller; G. Zulauf (International Journal of Earth Sciences, 2025)
The island of Donousa consists of a variegated metasedimentary sequence cut by arc-type granitoid dykes. Detrital zircon U–Pb ages and the presence of volcanic and ultramafic detritus suggest that the protoliths of the metasedimentary rocks were deposited in a Campanian forearc basin later than 76 Ma. D1 stacking of the forearc deposits occurred at upper crustal levels (P max = 0.4 GPa) with staurolite present as a stable phase. The subsequent isobaric heating led to growth of andalusite followed by D2 extension in the stability field of sillimanite, K-feldspar and high-quartz ( P = 0.3 GPa, T = 660 °C). Based on U–Pb ages of garnet (74.6 + 2.3/ − 2.5 Ma) and zircon (74.0 ± 0.8 Ma), separated from an early monzogranite dyke, the timing of forearc deposition, Buchan metamorphism, D2 extension and dyke emplacement is constrained to a maximum period of 2.6 m.y. in the late Campanian. Cooling below T = ca. 600 °C occurred during the Maastrichtian (71.3 + 0.6/ − 1.3 Ma, U–Pb on titanite) and was followed by D3 folding under greenschist facies conditions. A younger generation of Danian granitoid dykes (64.1 + 0.9/ − 1.4 Ma, U–Pb on titanite; 60 ± 4 Ma, Rb–Sr on muscovite) intruded at higher structural levels and was associated with a pervasive fluid-assisted overprint. The sequence of forearc deposition, burying, Buchan metamorphism, extension, and igneous dyking within < 2.6 m.y. is strong evidence for fast (ca. 4 cm a −1 ) trenchward arc retreat that was probably related to late Campanian subduction accretion and magmatic flare-up. Graphical abstract

Incorporation of needleleaf traits improves estimation of light absorption and gross primary production of evergreen needleleaf forests - Baihong Pan; Xiangming Xiao; Li Pan; Cheng Meng; Peter D. Blanken; Sean P. Burns; Jorge A. Celis; Chenchen Zhang; Yuanwei Qin (Agricultural and Forest Meteorology, 2025)

Extreme Drought Decreases the Stability of Above‐ but Not Below‐Ground Productivity Across Eurasian Steppes - Yingjie Yan; Chong Xu; Yann Hautier; Hongqiang Wang; Yuguang Ke; Honghui Wu; Jinsong Wang; Changjin Cheng; Xiaoan Zuo; Wentao Luo; Melinda D. Smith; Alan K. Knapp; et al. (Global Change Biology, 2025)
Ecological stability plays a crucial role in determining the sustainability of ecosystem functioning and nature's contribution to people. Although the disruptive effects of extreme drought on ecosystem structure and functions are widely recognized, their effect on the stability of above‐ and belowground productivity remains understudied. We assessed the effects of drought on ecosystem stability using a 3‐year drought experiment established in six Eurasian steppe grasslands. The treatments imposed included ambient precipitation, chronic drought (66% reduction in precipitation throughout the growing season), and intense drought (complete exclusion of precipitation for two months during the growing season). We found that drought, irrespective of how it was imposed, reduced the stability of aboveground net primary productivity (ANPP) but had little impact on belowground net primary productivity (BNPP) stability. Reduced ANPP stability under drought was primarily attributed to changes in subordinate species stability, with mean annual precipitation (MAP) and its variability, historical drought frequency, and the aridity index (AI) also influencing responses to extreme drought. In contrast, BNPP stability was not related to any community factor investigated, but it was influenced by MAP variability and AI. Our findings that above‐ and belowground productivity stability in grasslands are differentially sensitive to multi‐year extreme drought under both common (MAP and AI) as well as unique drivers (plant community changes) highlight the complexity of predicting carbon cycle dynamics as hydrological extremes become more severe.

Spatiotemporal variations in rural and urban beach microplastics accumulation in sediment along Sarangani Bay Protected Seascape, Mindanao, the Philippines - Arlene S. Escañan; Ming-Huang Wang; Frank T. Acot; Zy D. Perpetua; Recca E. Sajorne; Frank Paolo Jay B. Albarico; Chiu-Wen Chen; Cheng-Di Dong; Hernando P. Bacosa (Environmental Monitoring and Assessment, 2025)

Imaging brain white matter function using resting-state functional MRI - Gong-Jun Ji; Zaixu Cui; Ryan C.N. D’Arcy; Wei Liao; Bharat B. Biswal; Qing Zhang; Cheng Luo; Yu-Feng Zang; Zhaohua Ding; Xi-Nian Zuo; John C. Gore; Kai Wang (Science Bulletin, 2025)

Developing nondestructive sensitive detection for smoke-exposure assessment in wine via advanced Raman spectroscopy - Alec Sobotka; Taylor D. Krueger; Janak Solaris; Cheng Chen; Ye Feng; Steven G. Mayer; Yan Ping Qian; Chong Fang; Michael C. Qian (Food Chemistry, 2025)

Using DNA metabarcoding to assess insect diversity in grasslands - Changjin Lin; Haibin Han; Kejian Lin; Hongmei Cheng; Luyao Fu; Muhammad Ashfaq; Paul D. N. Hebert; Chenxi Liu (Applied Entomology and Zoology, 2025)

Disentangling metal diffusion from a highly industrial harbor and its bioaccumulation in different zooplankton groups - Mark Ariel D. Malto; Yee Cheng Lim; Chiu-Wen Chen; Ming-Huang Wang; Chih-Feng Chen; Frank Paolo Jay B. Albarico; Cheng-Di Dong (Marine Pollution Bulletin, 2025)

Astrometric observations of Phoebe from 2010 to 2019 based on Gaia DR3 - D. Yan; R.C. Qiao; X. Cheng; H.Y. Zhang; Y. Yu (Icarus, 2025)

Unique cortical morphology in young adults who are diagnosed with and medicated for attention-deficit/hyperactivity disorder - Madeleine K. Nowak; William G. Kronenberger; Jiancheng Hou; Osamudiamen Ogbeide; Lillian M. Klemsz; Hu Cheng; Sharlene D. Newman; Keisuke Kawata (Brain Imaging and Behavior, 2025)

Observations, perceptions and concerns of the American lobster industry regarding the range-expansion of Black Sea Bass - Helen Cheng; Marissa D. McMahan; Steven B. Scyphers; Loren McClenachan; Jonathan H. Grabowski (Marine Policy, 2025)

Selective production of olefins from methanol over a heteroatomic SAPO-34 zeolite - Zhaodong Zhu; Mengtian Fan; Meng He; Bing An; Yinlin Chen; Shaojun Xu; Tianze Zhou; Alena M. Sheveleva; Meredydd Kippax-Jones; Lutong Shan; Yongqiang Cheng; Hamish Cavaye; et al. (Science Bulletin, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Prehistoric human hand and footprints in Quesang on the central Tibetan Plateau from the Bølling-Allerød Interstadial - Yuhai Gao; David D. Zhang; Haiwei Zhang; Shengda Zhang; Teng Li; Shimin Chen; Chengcai Luo; Hai Cheng (Archaeological and Anthropological Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Combined effect of acidification temperature and different acids on microstructure and textural properties of heat and acid-induced milk gels - Zhe Cheng; Wenjie Xia; Pauline van Leusden; Tomasz Pawel Czaja; Matthias D. Eisner; Lilia Ahrné (International Dairy Journal, 2025)

Integrating multi-faceted approaches in malacofauna diversity changes: Insights on ecological and resource management in a data-limited developing country - Mark Ariel D. Malto; Frank Paolo Jay B. Albarico; Yee Cheng Lim; Chih-Feng Chen; Genese Divine B. Cayabo; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Novel hydrothermal modification to alter functionality and reduce glycemic response of pea starch - Fan Cheng; Gexiao Sun; Xuehong Li; Thomas D. Warkentin; Yongfeng Ai (Carbohydrate Polymers, 2025)

Relative Residence Time Can Account for Half of the Anatomical Variation in Fatty Streak Prevalence Within the Right Coronary Artery - Pratik Kandangwa; Kevin Cheng; Miten Patel; Spencer J. Sherwin; Ranil de Silva; Peter D. Weinberg (Annals of Biomedical Engineering, 2025)
Purpose The patchy anatomical distribution of atherosclerosis has been attributed to variation in haemodynamic wall shear stress (WSS). The consensus is that low WSS and a high Oscillatory Shear Index (OSI) trigger the disease. We found that atherosclerosis at aortic branch sites correlates threefold better with transverse WSS (transWSS), a metric which quantifies multidirectional near-wall flow. Coronary artery disease has greater clinical significance than aortic disease but computation of WSS metrics is complicated by the substantial vessel motion occurring during each cardiac cycle. Here we present the first comparison of the distribution of atherosclerosis with WSS metrics computed for moving coronary arteries. Methods Maps of WSS metrics were computed using dynamic geometries reconstructed from angiograms of ten non-stenosed human right coronary arteries (RCAs). They were compared with maps of fatty streak prevalence derived from a previous study of 1852 RCAs. Results Time average WSS (TAWSS), OSI, transWSS and the cross-flow index (CFI), a non-dimensional form of the transWSS, gave non-significant or significant but low spatial correlations with lesion prevalence. The highest correlation coefficient (0.71) was for the relative residence time (RRT), a metric that decreases with TAWSS and increases with OSI. The coefficient was not changed if RRT was calculated using CFI, which captures multidirectional WSS only, rather than OSI, which encompasses both multidirectional and oscillatory WSS. Conclusion Contrary to our earlier findings in the aorta, low WSS in combination with highly multidirectional flow correlates best with lesion location in the RCA, explaining approximately half of its anatomical variation.

Perceptions of swine industry stakeholders on the use of water-based foam, high-expansion nitrogen foam, and carbon dioxide gas as methods of swine depopulation - Janice Y. Park; Magnus R. Campler; Ting-Yu Cheng; Justin D. Kieffer; Andréia G. Arruda; Madonna E. Benjamin; Dale W. Rozeboom; Andrew S. Bowman (Preventive Veterinary Medicine, 2024)

Economics-constrained tidal turbine array layout optimisation at the Putuoshan–Hulu island waterway - Can Zhang; Xiaoming Cheng; Athanasios Angeloudis; Stephan C. Kramer; Chengsheng Wu; Ying Chen; Matthew D. Piggott (Ocean Engineering, 2024)

North Atlantic Heat Transport Convergence Derived from a Regional Energy Budget Using Different Ocean Heat Content Estimates - B. Meyssignac; S. Fourest; Michael Mayer; G. C. Johnson; F. M. Calafat; M. Ablain; T. Boyer; L. Cheng; D. Desbruyères; G. Forget; D. Giglio; M. Kuusela; et al. (Surveys in Geophysics, 2024)
This study uses an oceanic energy budget to estimate the ocean heat transport convergence in the North Atlantic during 2005–2018. The horizontal convergence of the ocean heat transport is estimated using ocean heat content tendency primarily derived from satellite altimetry combined with space gravimetry. The net surface energy fluxes are inferred from mass-corrected divergence of atmospheric energy transport and tendency of the ECMWF ERA5 reanalysis combined with top-of-the-atmosphere radiative fluxes from the clouds and the Earth’s radiant energy system project. The indirectly estimated horizontal convergence of the ocean heat transport is integrated between the rapid climate change-meridional overturning circulation and heatflux array (RAPID) section at 26.5°N (operating since 2004) and the overturning in the subpolar north atlantic program (OSNAP) section, situated at 53°–60°N (operating since 2014). This is to validate the ocean heat transport convergence estimate against an independent estimate derived from RAPID and OSNAP in-situ measurements. The mean ocean energy budget of the North Atlantic is closed to within ± 0.25 PW between RAPID and OSNAP sections. The mean oceanic heat transport convergence between these sections is 0.58 ± 0.25 PW, which agrees well with observed section transports. Interannual variability of the inferred oceanic heat transport convergence is also in reasonable agreement with the interannual variability observed at RAPID and OSNAP, with a correlation of 0.54 between annual time series. The correlation increases to 0.67 for biannual time series. Other estimates of the ocean energy budget based on ocean heat content tendency derived from various methods give similar results. Despite a large spread, the correlation is always significant meaning the results are robust against the method to estimate the ocean heat content tendency.

Successful Invasion Into New Environments Without Evidence of Rapid Adaptation by a Predatory Marine Gastropod - Blair P. Bentley; Brian S. Cheng; Reid S. Brennan; John D. Swenson; Jamie L. Adkins; Andrew R. Villeneuve; Lisa M. Komoroske (Molecular Ecology, 2024)
Invasive species with native ranges spanning strong environmental gradients are well suited for examining the roles of selection and population history in rapid adaptation to new habitats, providing insight into potential evolutionary responses to climate change. The Atlantic oyster drill ( Urosalpinx cinerea ) is a marine snail whose native range spans the strongest coastal latitudinal temperature gradient in the world, with invasive populations established on the US Pacific coast. Here, we leverage this system using genome‐wide SNPs and environmental data to examine invasion history and identify genotype–environment associations indicative of local adaptation across the native range, and then assess evidence for allelic frequency shifts that would signal rapid adaptation within invasive populations. We demonstrate strong genetic structuring among native regions which aligns with life history expectations, identifying southern New England as the source of invasive populations. Then, we identify putatively thermally adaptive loci across the native range but find no evidence of allele frequency shifts in invasive populations that suggest rapid adaptation to new environments. Our results indicate that while these loci may underpin local thermal adaptation in their native range, selection is relaxed in invasive populations, perhaps due to complex polygenic architecture underlying thermal traits and/or standing capacity for phenotypic plasticity. Given the prolific invasion of Urosalpinx , our study suggests population success in new environments is influenced by factors other than selection on standing genetic variation that underlies local adaptation in the native range and highlights the importance of considering population history and environmental selection pressures when evaluating adaptive capacity.

Long-term evolution of the Sulzberger Ice Shelf, West Antarctica: Insights from 74-year observations and 2022 Hunga-Tonga volcanic tsunami-induced calving - Aiguo Zhao; Yuan Cheng; Alexander D. Fraser; Luke G. Bennetts; Haifeng Xiao; Qi Liang; Teng Li; Rongxing Li (Earth and Planetary Science Letters, 2024)

Cascade effects of global supply chains induced by regional conflicts increase global inequality - Rongtian Zhao; Daoping Wang; Yong Ge; Mo Zhang; Die Zhang; D'Maris Coffman; Qiuming Cheng (Resources, Conservation and Recycling, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Fabrication of a label-free electrochemical immunosensor by functionalized nanofiber membrane for the ultrasensitive detection of quinalphos - Jian-cheng Hu; Peng Wen; Yu Wang; Jin-yi Yang; Zhi-li Xiao; Zhen-lin Xu; Yu-dong Shen; Hong Wang; Bruce D. Hammock (Food Control, 2024)

A Panel of miRNA Biomarkers Common to Serum and Brain-Derived Extracellular Vesicles Identified in Mouse Model of Amyotrophic Lateral Sclerosis - Natasha Vassileff; Jereme G. Spiers; John D. Lee; Trent M. Woodruff; Esmaeil Ebrahimie; Manijeh Mohammadi Dehcheshmeh; Andrew F. Hill; Lesley Cheng (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is a progressive motor neuron disease characterised by the deposition of aggregated proteins including TAR DNA-binding protein 43 (TDP-43) in vulnerable motor neurons and the brain. Extracellular vesicles (EVs) facilitate the spread of neurodegenerative diseases and can be easily accessed in the bloodstream. This study aimed to identify a panel of EV miRNAs that can capture the pathology occurring in the brain and peripheral circulation. EVs were isolated from the cortex (BDEVs) and serum (serum EVs) of 3 month-old and 6-month-old TDP-43*Q331K and TDP-43*WT mice. Following characterisation and miRNA isolation, the EVs underwent next-generation sequencing where 24 differentially packaged miRNAs were identified in the TDP-43*Q331K BDEVs and 7 in the TDP-43*Q331K serum EVs. Several miRNAs, including miR-183-5p, were linked to ALS. Additionally, miR-122-5p and miR-486b-5p were identified in both panels, demonstrating the ability of the serum EVs to capture the dysregulation occurring in the brain. This is the first study to identify miRNAs common to both the serum EVs and BDEVs in a mouse model of ALS.

Number of global change factors alters plant-soil feedbacks via its effect on soil fungal communities - Wei Xue; Lin Huang; James D. Bever; Cheng Du; Hao-Ming Yuan; Lin-Xuan He; Xiao-Mei Zhang; Fei-Hai Yu (Soil Biology and Biochemistry, 2024)

Small iridium clusters supported on TiO2 as catalysts for intensifying low-temperature methane activation and reforming - Hou-Jen Lai; Yu-Cheng Liu; Santhanamoorthi Nachimuthu; Shawn D. Lin; Jyh-Chiang Jiang (Chemical Engineering Journal, 2024)

Limited exposure of captive Australian marsupials to plastics - Elvis D. Okoffo; Wei-Cheng Lu; Emma Yenney; Kevin V. Thomas (Science of The Total Environment, 2024)

Exposure to outdoor ambient air toxics and risk of breast cancer: The multiethnic cohort - Julia E. Heck; Di He; Sam E. Wing; Beate Ritz; Chandra D. Carey; Juan Yang; Daniel O. Stram; Loïc Le Marchand; Sungshim Lani Park; Iona Cheng; Anna H. Wu (International Journal of Hygiene and Environmental Health, 2024)

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

A preliminary assessment of CO2 capture, transport, and storage network for China's steel sector - Yuancheng Lin; Tubagus Aryandi Gunawan; Cecelia Isaac; Hongxi Luo; Fangwei Cheng; Eric D. Larson; Chris Greig; Linwei Ma; Zheng Li (Journal of Cleaner Production, 2024)

Capturing uncertainty when modelling environmental drivers of fish populations, with an illustrative application to Pacific Cod in the eastern Bering Sea - André E. Punt; Michael G. Dalton; Grant D. Adams; Steven J. Barbeaux; Wei Cheng; Albert J. Hermann; Kirstin K. Holsman; Peter-John F. Hulson; Thomas P. Hurst; Alberto Rovellini (Fisheries Research, 2024)

Polyethylene microplastics induced lipidomic responses in Chironomus tepperi: A two-generational exploration - Hsuan-Cheng Lu; Steven D. Melvin; Shima Ziajahromi; Peta A. Neale; Frederic D.L. Leusch; Anupama Kumar (Science of The Total Environment, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Enzymatic metal oxide/nanoparticle heterojunctions with mutually reinforced bifunctional chemotherapies for combating drug-resistant bacteria - Qian Zhou; Ting Wang; Zhenyu Xing; Raul D. Rodriguez; Liang Cheng; Yang Gao; Qiu Chen; Chong Cheng (Chemical Engineering Journal, 2024)

Distinct bile acid alterations in response to a single administration of PFOA and PFDA in mice - Xiaoxiao Yu; Youcai Zhang; Bruno Cogliati; Curtis D. Klaassen; Sanaya Kumar; Xingguo Cheng; Pengli Bu (Toxicology, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Highly discrepant Lu–Hf and Sm–Nd dates from crustal xenoliths witness the stability and destruction of a craton - Hao Cheng; Elias M. Bloch; Evangelos Moulas; Jeffrey D. Vervoort; Wen-Liang Xu; Kai-Yang Du (Earth and Planetary Science Letters, 2024)

PARSIFAL: A toolkit for triple-GEM parametrized simulation - A. Amoroso; R. Baldini Ferroli; I. Balossino; M. Bertani; D. Bettoni; F. Bianchi; A. Bortone; A. Calcaterra; S. Cerioni; W. Cheng; G. Cibinetto; A. Cotta Ramusino; et al. (Computer Physics Communications, 2024)

A novel bluetongue virus serotype 2 strain isolated from a farmed Florida white-tailed deer (Odocoileus virginianus) arose from reassortment of gene segments derived from co-circulating serotypes in the Southeastern USA - Pedro H. O. Viadanna; Austin Surphlis; An-Chi Cheng; Catherine E. Dixon; Sarah Meisner; Kristen N. Wilson; Zoe S. White; Emily DeRuyter; Tracey D. Logan; Juan M. C. Krauer; John A. Lednicky; Samantha M. Wisely; et al. (Virus Genes, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

Heat-moisture treatment to modify structure and functionality and reduce digestibility of wrinkled and round pea starches - Fan Cheng; Yikai Ren; Thomas D. Warkentin; Yongfeng Ai (Carbohydrate Polymers, 2024)

Net greenhouse gas balance in U.S. croplands: How can soils be part of the climate solution? - Yongfa You; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; William D. Batchelor; Bo Cheng; Dafeng Hui; David Kicklighter; Xin‐Zhong Liang; Xiaoyong Li; Jerry Melillo; et al. (Global Change Biology, 2024)
Agricultural soils play a dual role in regulating the Earth's climate by releasing or sequestering carbon dioxide (CO 2 ) in soil organic carbon (SOC) and emitting non‐CO 2 greenhouse gases (GHGs) such as nitrous oxide (N 2 O) and methane (CH 4 ). To understand how agricultural soils can play a role in climate solutions requires a comprehensive assessment of net soil GHG balance (i.e., sum of SOC‐sequestered CO 2 and non‐CO 2 GHG emissions) and the underlying controls. Herein, we used a model‐data integration approach to understand and quantify how natural and anthropogenic factors have affected the magnitude and spatiotemporal variations of the net soil GHG balance in U.S. croplands during 1960–2018. Specifically, we used the dynamic land ecosystem model for regional simulations and used field observations of SOC sequestration rates and N 2 O and CH 4 emissions to calibrate, validate, and corroborate model simulations. Results show that U.S. agricultural soils sequestered Tg CO 2 ‐C year −1 in SOC (at a depth of 3.5 m) during 1960–2018 and emitted Tg N 2 O‐N year −1 and Tg CH 4 ‐C year −1 , respectively. Based on the GWP100 metric (global warming potential on a 100‐year time horizon), the estimated national net GHG emission rate from agricultural soils was Tg CO 2 ‐eq year −1 , with the largest contribution from N 2 O emissions. The sequestered SOC offset ~28% of the climate‐warming effects resulting from non‐CO 2 GHG emissions, and this offsetting effect increased over time. Increased nitrogen fertilizer use was the dominant factor contributing to the increase in net GHG emissions during 1960–2018, explaining ~47% of total changes. In contrast, reduced cropland area, the adoption of agricultural conservation practices (e.g., reduced tillage), and rising atmospheric CO 2 levels attenuated net GHG emissions from U.S. croplands. Improving management practices to mitigate N 2 O emissions represents the biggest opportunity for achieving net‐zero emissions in U.S. croplands. Our study highlights the importance of concurrently quantifying SOC‐sequestered CO 2 and non‐CO 2 GHG emissions for developing effective agricultural climate change mitigation measures.

Intracellular iron accumulation facilitates mycobacterial infection in old mouse macrophages - Stephen K. Kotey; Xuejuan Tan; Owen Fleming; Ramakrishnama Raju Kasiraju; Audrey L. Dagnell; Kyle N. Van Pelt; Janet Rogers; Steven D. Hartson; Nidheesh Thadathil; Ramasamy Selvarani; Rojina Ranjit; Sreemathi Logan; et al. (GeroScience, 2023)
Aging has a significant impact on the immune system, leading to a gradual decline in immune function and changes in the body’s ability to respond to bacterial infections. Non-tuberculous mycobacteria (NTM), also known as atypical mycobacteria or environmental mycobacteria, are commonly found in soil, water, and various environmental sources. While many NTM species are considered opportunistic pathogens, some can cause significant infections, particularly in individuals with compromised immune systems, such as older individuals. When mycobacteria enter the body, macrophages are among the first immune cells to encounter them and attempt to engulf mycobacteria through a process called phagocytosis. Some NTM species, including Mycobacterium avium ( M. avium ) can survive and replicate within macrophages. However, little is known about the interaction between NTM and macrophages in older individuals. In this study, we investigated the response of bone marrow–derived macrophage (BMMs) isolated from young (5 months) and old (25 months) mice to M. avium serotype 4, one of the main NTM species in patients with pulmonary NTM diseases. Our results demonstrated that BMMs from old mice have an increased level of intracellular iron and are more susceptible to M. avium serotype 4 infection compared to BMMs from young mice. The whole-cell proteomic analysis indicated a dysregulated expression of iron homeostasis–associated proteins in old BMMs regardless of mycobacterial infection. Deferoxamine, an iron chelator, significantly rescued mycobacterial killing and phagolysosome maturation in BMMs from old mice. Therefore, our data for the first time indicate that an intracellular iron accumulation improves NTM survival within macrophages from old mice and suggest a potential application of iron-chelating drugs as a host-directed therapy for pulmonary NTM infection in older individuals.

Enhancement of bio-S0 recovery and revealing the inhibitory effect on microorganisms under high sulfide loading - Junjie Wang; Zhuowei Cheng; Jiade Wang; Dongzhi Chen; Jianmeng Chen; Jianming Yu; Songkai Qiu; Dionysios D. Dionysiou (Environmental Research, 2023)

The osmotic stress of Vallisneria natans (Lour.) Hara leaves originating from the disruption of calcium and potassium homeostasis caused by MC-LR - Chen Cheng; Alan D. Steinman; Qingju Xue; Lei Zhang; Liqiang Xie (Water Research, 2023)

Metabolomic responses in freshwater benthic invertebrate, Chironomus tepperi, exposed to polyethylene microplastics: A two-generational investigation - Hsuan-Cheng Lu; Anupama Kumar; Steven D. Melvin; Shima Ziajahromi; Peta A. Neale; Frederic D.L. Leusch (Journal of Hazardous Materials, 2023)

Genetic deletion or pharmacological inhibition of soluble epoxide hydrolase attenuated particulate matter 2.5 exposure mediated lung injury - Juan Zhang; Wen-Hao Zhang; Christophe Morisseau; Min Zhang; Hong-Jun Dong; Qi-Meng Zhu; Xiao-Kui Huo; Cheng-Peng Sun; Bruce D. Hammock; Xiao-Chi Ma (Journal of Hazardous Materials, 2023)

A study of cyanidin/alginate complexation: Influence of pH in assembly and chiral properties - Nattida Chotechuang; Paolo Di Gianvincenzo; Cheng Giuseppe Chen; Alessandro Nicola Nardi; Daniel Padró; Chanchai Boonla; Maria Grazia Ortore; Marco D' Abramo; Sergio E. Moya (Carbohydrate Polymers, 2023)

Air quality improvement assessment and exposure risk of Shandong Province in China during 2014 to 2020 - N. N. Wang; C. Y. Zhu; Wei Li; M. Y. Qiu; B. L. Wang; X. Y. Li; B. D. Jiang; X. Y. Qu; Z. S. Li; H. C. Cheng (International Journal of Environmental Science and Technology, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Refinement of water-based foam depopulation procedures for finisher pigs during field conditions: Welfare implications and logistical aspects - Magnus R. Campler; Ting-Yu Cheng; Andréia G. Arruda; Mark Flint; Justin D. Kieffer; Brad Youngblood; Andrew S. Bowman (Preventive Veterinary Medicine, 2023)

Environmental optima for common diatoms from Ontario lakes along gradients of lakewater pH, total phosphorus concentration, and depth - Matthew P. Duda; Branaavan Sivarajah; Kathleen M. Rühland; Andrew M. Paterson; Jennifer L. Barrow; Yuanyu Cheng; Elizabeth J. Favot; Kristopher R. Hadley; Roland I. Hall; Kathryn E. Hargan; Clare Nelligan; Euan D. Reavie; et al. (Journal of Paleolimnology, 2023)

Bacterial community assembly and antibiotic resistance genes in soils exposed to antibiotics at environmentally relevant concentrations - Zeyou Chen; Wei Zhang; Anping Peng; Yike Shen; Xin Jin; Robert D. Stedtfeld; Stephen A. Boyd; Brian J. Teppen; James M. Tiedje; Cheng Gu; Dongqiang Zhu; Yi Luo; et al. (Environmental Microbiology, 2023)
Understanding how bacterial community assembly and antibiotic resistance genes (ARGs) respond to antibiotic exposure is essential to deciphering the ecological risk of anthropogenic antibiotic pollution in soils. In this study, three loam soils with different land management (unmanured golf course, dairy‐manured pasture, and swine‐manured cornfield) were spiked with a mixture of 11 antibiotics at the initial concentration of 100 and 1000 μg kg −1 for each antibiotic and incubated over 132 days, mimicking a scenario of pulse disturbance and recovery in soils, with unspiked soil samples as the control treatment. The Infer Community Assembly Mechanisms by Phylogenetic‐bin‐based null model (iCAMP) analysis demonstrated that drift and dispersal limitation contributed to 57%–65% and 16%–25%, and homogeneous selection 12%–16% of soil bacterial community assembly. Interestingly, antibiotic exposure to 1000 μg kg −1 level significantly increased the contribution of drift to community assembly, largely due to the positive response from Acidobacteria‐6 in the golf course and pasture soils and from Chthoniobacteraceae in the cornfield soil to the antibiotic exposure. However, ARG abundance and diversity in the three soils exhibited antibiotics‐independent temporal fluctuations, but were associated with the changes in soil bacterial communities over time. This study provides the first insight into the relative contributions of different bacterial community assembly processes in soils upon antibiotic exposure at environmentally relevant concentrations.

Natural microfibrils/regenerated cellulose-based carbon aerogel for highly efficient oil/water separation - Xiang Ma; Shuang Zhou; Junting Li; Fei Xie; Hui Yang; Cheng Wang; Bradley D. Fahlman; Wenjiang Li (Journal of Hazardous Materials, 2023)

Comparative Analysis of Rhizosphere and Endophytic Microbial Communities Between Root Rot and Healthy Root of Psammosilene tunicoides - Wen. T. Yang; Guo. D. Li; Jun. N. Li; Cheng. F. Yang; Xiao. M. Zhang; Ai. L. Zhang (Current Microbiology, 2023)
The wild resources of Psammosilene tunicoides have decreased sharply because of the long-term mining and excavation, which has led to the increased demand for its artificial cultivation. However, root rot represents a significant obstacle leading to a poor quality and product of P. tunicoides . Previous reports have not focused on root rot in P. tunicoides. Therefore, this study explores the rhizospheric and root endophytic microbial community structure and composition of healthy and root rot P. tunicoides to understand the mechanism underlying root rot . The properties of the rhizosphere soil were assessed using physiochemical methods, and the bacterial and fungal populations were studied through amplicon sequencing of the 16S rRNA genes and ITS regions in the root and soil. Compared to healthy samples, the pH, hydrolysis N, available P, and available K were significantly decreased in the diseased samples while the organic matter and total organic carbon were significantly increased in the diseased samples. Redundancy analysis (RDA) showed that soil environmental factors are related to changes in the root and rhizosphere soil microbial community of P. tunicoides indicating that the physiochemical properties of soil affect plant health. Alpha diversity analysis showed that the microbial communities of healthy and diseased samples were similar. Some bacterial and fungal genera were significantly increased or decreased ( P < 0.05) in diseased P. tunicoides , and certain microbial factors that antagonized root rot were further explored. This study provides an abundant microbial resource for future studies and contributes to improving soil quality and P. tunicoides agricultural production.

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Championing inclusive terminology in ecology and evolution - Susan J. Cheng; Kaitlyn M. Gaynor; Alex C. Moore; Kathy Darragh; Cesar O. Estien; J.W. Hammond; Christopher Lawrence; Kirby L. Mills; Marcella D. Baiz; Danielle Ignace; Lily Khadempour; Matthew A. McCary; et al. (Trends in Ecology & Evolution, 2023)

Risk assessment and identification of factors influencing the historical concentrations of microcystin in Lake Taihu, China - Chen Cheng; Alan D. Steinman; Kaiye Zhang; Qi Lin; Qingju Xue; Xing Wang; Liqiang Xie (Journal of Environmental Sciences, 2023)

L-carnitine enhances developmental potential of bovine oocytes matured under high lipid concentrations in vitro - Giovana D. Catandi; Ming-Hao Cheng; Adam J. Chicco; Tom Chen; Elaine M. Carnevale (Animal Reproduction Science, 2023)

Insights into performance and mechanism of ZnO/CuCo2O4 composite as heterogeneous photoactivator of peroxymonosulfate for enrofloxacin degradation - Junjing Li; Xiuwen Cheng; Huixuan Zhang; Jianfeng Gou; Xinyi Zhang; Di Wu; Dionysios D. Dionysiou (Journal of Hazardous Materials, 2023)

Stratigraphic revision of the early Miocene Kiahera Formation from Rusinga Island, Lake Victoria, Kenya - Lauren A. Michel; Daniel J. Peppe; Kimberly D. Cheng; Hunter Summers; H. Wayne Leimer; Thomas Lehmann; Samuel Muteti; Kieran P. McNulty (Journal of African Earth Sciences, 2023)

DOK7 Promotes NMJ Regeneration After Nerve Injury - Ethan D. Kosco; Hongyang Jing; Peng Chen; Wen-Cheng Xiong; Ivy S. Samuels; Lin Mei (Molecular Neurobiology, 2023)

Quantifying long‐term phenological patterns of aerial insectivores roosting in the Great Lakes region using weather surveillance radar - Yuting Deng; Maria Carolina T. D. Belotti; Wenlong Zhao; Zezhou Cheng; Gustavo Perez; Elske Tielens; Victoria F. Simons; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Change Biology, 2023)
Organisms have been shifting their timing of life history events (phenology) in response to changes in the emergence of resources induced by climate change. Yet understanding these patterns at large scales and across long time series is often challenging. Here we used the US weather surveillance radar network to collect data on the timing of communal swallow and martin roosts and evaluate the scale of phenological shifts and its potential association with temperature. The discrete morning departures of these aggregated aerial insectivores from ground‐based roosting locations are detected by radars around sunrise. For the first time, we applied a machine learning algorithm to automatically detect and track these large‐scale behaviors. We used 21 years of data from 12 weather surveillance radar stations in the Great Lakes region to quantify the phenology in roosting behavior of aerial insectivores at three spatial levels: local roost cluster, radar station, and across the Great Lakes region. We show that their peak roosting activity timing has advanced by 2.26 days per decade at the regional scale. Similar signals of advancement were found at the station scale, but not at the local roost cluster scale. Air temperature trends in the Great Lakes region during the active roosting period were predictive of later stages of roosting phenology trends (75% and 90% passage dates). Our study represents one of the longest‐term broad‐scale phenology examinations of avian aerial insectivore species responding to environmental change and provides a stepping stone for examining potential phenological mismatches across trophic levels at broad spatial scales.

Bioactive compounds, health benefits, and industrial applications of Tartary buckwheat ( Fagopyrum tataricum ) - Liang Zou; Dingtao Wu; Guixing Ren; Yichen Hu; Lianxin Peng; Jianglin Zhao; Pascual Garcia-Perez; Maria Carpena; Miguel A. Prieto; Hui Cao; Ka-Wing Cheng; Mingfu Wang; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

Development of a prey-predator species distribution model for a large piscivorous fish: A case study for Japanese Spanish mackerel Scomberomorus niphonius and Japanese anchovy Engraulis japonicus - Shuhao Liu; Yongjun Tian; Yang Liu; Irene D. Alabia; Jiahua Cheng; Shin-ichi Ito (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Silkworm cocoon waste-derived nitrogen-doped hierarchical porous carbon as robust electrode materials for efficient capacitive desalination - Su-Mei Zheng; Zhi-Hua Yuan; Dionysios D. Dionysiou; Lu-Bin Zhong; Fei Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Chemical Engineering Journal, 2023)

Anthropomorphic model rigid loading indenter with embedded sensor development for wheelchair cushion standard testing - Cheng-Shiu Chung; Garrett G. Grindle; Joshua D. Brown; Benjamin Gebrosky; Wei Carrigan; Pavan Nuthi; Muthu B. J. Wijesundara; Rory A. Cooper (Medical & Biological Engineering & Computing, 2023)

What SES may explain about work-related health limitations: A temporal-ordered model - Celia C. Lo; Paul D. C. Bones; Tyrone C. Cheng (The Social Science Journal, 2023)

In situ laser-assisted synthesis and patterning of graphene foam composites as a flexible gas sensing platform - Jiang Zhao; Ning Yi; Xiaohong Ding; Shangbin Liu; Jia Zhu; Alexander C. Castonguay; Yuyan Gao; Lauren D. Zarzar; Huanyu Cheng (Chemical Engineering Journal, 2023)

The disruption of calcium and hydrogen ion homeostasis of submerged macrophyte Vallisneria natans (Lour.) Hara caused by microcystin-LR - Chen Cheng; Alan D. Steinman; Qingju Xue; Xiang Wan; Liqiang Xie (Aquatic Toxicology, 2023)

Complex impacts of hydraulic fracturing return fluids on soil microbial community respiration, structure and functional potentials - Cheng Zhong; Camilla L. Nesbø; Konstantin von Gunten; Yifeng Zhang; Xiaoqing Shao; Rong Jin; Kurt O. Konhauser; Greg G. Goss; Jonathan W. Martin; Yuhe He; Pei‐Yuan Qian; Brian D. Lanoil; et al. (Environmental Microbiology, 2022)
Summary The consequences of soils exposed to hydraulic fracturing (HF) return fluid, often collectively termed flowback and produced water (FPW), are poorly understood, even though soils are a common receptor of FPW spills. Here, we investigate the impacts on soil microbiota exposed to FPW collected from the Montney Formation of western Canada. We measured soil respiration, microbial community structure and functional potentials under FPW exposure across a range of concentrations, exposure time and soil types (luvisol and chernozem). We find that soil type governs microbial community response upon FPW exposure. Within each soil, FPW exposure led to reduced biotic soil respiration, and shifted microbial community structure and functional potentials. We detect substantially higher species richness and more unique functional genes in FPW‐exposed soils than in FPW‐unexposed soils, with metagenome‐assembled genomes (e.g. Marinobacter persicus ) from luvisol soil exposed to concentrated FPW being most similar to genomes from HF/FPW sites. Our data demonstrate the complex impacts of microbial communities following FPW exposure and highlight the site‐specific effects in evaluation of spills and agricultural reuse of FPW on the normal soil functions.

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genotype-Environment-Management Interactions in Biomass Yield and Feedstock Composition of Photoperiod-Sensitive Energy Sorghum - August Schetter; Cheng-Hsien Lin; Colleen Zumpf; Chunhwa Jang; Leo Hoffmann; William Rooney; D. K. Lee (BioEnergy Research, 2022)

Quantifying cancer risk from exposures to medical imaging in the Risk of Pediatric and Adolescent Cancer Associated with Medical Imaging (RIC) Study: research methods and cohort profile - Marilyn L. Kwan; Diana L. Miglioretti; Erin J. A. Bowles; Sheila Weinmann; Robert T. Greenlee; Natasha K. Stout; Alanna Kulchak Rahm; Susan A. Alber; Priscila Pequeno; Lisa M. Moy; Carly Stewart; Cindy Fong; et al. (Cancer Causes & Control, 2022)

Hydrodynamic Performance of Full-Scale T0 and T90 Codends with and without a Codend Cover - Zhaohai Cheng; Paul D. Winger; Shannon M. Bayse; David Kelly (Journal of Marine Science and Engineering, 2022)
The hydrodynamic performance of one full-scale T0 (mesh size 90 mm) and three T90 (mesh size 90, 100, and 110 mm) codends was investigated and compared using flume tank testing, with and without a small-mesh cover. We evaluated how flow velocity, mesh circularity, and drag changed in each codend at five different towing speeds (0.5–0.9 m/s). The results demonstrated that flow velocity decreased along the length of a codend, and this effect was pronounced in the T0 codend. Increasing the mesh size of T90 codends from 90 to 110 mm did not significantly affect flow velocity. A novel parameter, termed mesh circularity, was developed and introduced to describe mesh opening. Mesh circularity in the T0 codend decreased along the length of the codend, which contrasted with the T90 codends. Results showed that the T90 codends maintained relatively open meshes (circularity ranged from ~0.8 to 1.0 along the length of the codend) compared to the T0 (circularity ranged from ~0.6 to 0.4). Each T90 codend had a significantly (p 0.05), but was significantly different for the T90 codend (p

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

Study on adsorption-degradation of 2,4-dichlorophenol by modified biochar immobilized laccase - Z. Wang; D. Ren; J. Wu; S. Jiang; H. Yu; Y. Cheng; S. Zhang; X. Zhang (International Journal of Environmental Science and Technology, 2022)

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

A genetic platform for predicting and reducing non-tenera contamination in oil palm (Elaeis guineensis) seed supply - Rajinder Singh; Leslie Cheng-Li Ooi; Ngoot-Chin Ting; Eng-Ti Leslie Low; Meilina Ong-Abdullah; Rajanaidu Nookiah; Marhalil Marjuni; Suzana Mustaffa; Mohamad Arif Abdul Manaf; Peggy Garner; Jerry Reed; Corey Wischmeyer; et al. (Tree Genetics & Genomes, 2021)

Porphyry Molybdenum Prospectivity in the Zhongdian Arc, SW China: Use of Singularity and Factor Analyses for Resource Assessment - Ohouo Rebecca Mondah; Qiuming Cheng; Jie Yang; Kadio Aka D. Koua (Natural Resources Research, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A Bayesian Multilevel Ordinal Regression Model for Fish Maturity Data: Difference in Maturity Ogives of Skipjack Tuna (Katsuwonus pelamis) Between Schools in the Western and Central Pacific Ocean - Jie Cao; Xuefang Wang; Matthew D. Damiano; Cheng Zhou; Jiangfeng Zhu (Frontiers in Marine Science, 2021)
The maturity ogive is vital to defining the fraction of a population capable of reproduction. In this study, we proposed a novel approach, a Bayesian multilevel ordinal regression (i.e., Bayesian continuation ratio model), to model the maturity ogive. The model assumes that the observed maturity stage originates from the categorization of latent continuous variables. We demonstrated this approach by testing whether there are differences in the maturity ogive of skipjack tuna ( Katsuonus pelamis ) in the western and central Pacific Ocean between two school types, i.e., free-swimming and floating-object-associated schools. The model results show that K. pelamis , given the same fork length, are more likely to have a higher maturity stage in a free-swimming school than those associated with floating objects. The gonadosomatic index revealed the same conclusion. Our results indicate that fish aggregation devices (FADs) could negatively affect the maturity of K. pelamis and consequently reduce the population reproductive potential. This study provides (1) an alternative approach to analyze fisheries ordinal data; (2) important quantitative evidence to evaluate the existing ecological hypotheses; and (3) implications for tuna fisheries management.

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

Keep your friends close: Host compartmentalisation of microbial communities facilitates decoupling from effects of habitat fragmentation - Claire E. Willing; Grady Pierroz; Aidee Guzman; Leander D. L. Anderegg; Cheng Gao; Devin Coleman‐Derr; John W. Taylor; Tom D. Bruns; Todd E. Dawson (Ecology Letters, 2021)
Root‐associated fungal communities modify the climatic niches and even the competitive ability of their hosts, yet how the different components of the root microbiome are modified by habitat loss remains a key knowledge gap. Using principles of landscape ecology, we tested how free‐living versus host‐associated microbes differ in their response to landscape heterogeneity. Further, we explore how compartmentalisation of microbes into specialised root structures filters for key fungal symbionts. Our study demonstrates that free‐living fungal community structure correlates with landscape heterogeneity, but that host‐associated fungal communities depart from these patterns. Specifically, biotic filtering in roots, especially via compartmentalisation within specialised root structures, decouples the biogeographic patterns of host‐associated fungal communities from the soil community. In this way, even as habitat loss and fragmentation threaten fungal diversity in the soils, plant hosts exert biotic controls to ensure associations with critical mutualists, helping to preserve the root mycobiome.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Biphasic Effects of Ethanol Exposure on Waste Metabolites Clearance in the CNS - Yiming Cheng; Xiaotang Ma; Kevin D. Belfield; James Haorah (Molecular Neurobiology, 2021)

Extreme weather events and dengue outbreaks in Guangzhou, China: a time-series quasi-binomial distributed lag non-linear model - Jian Cheng; Hilary Bambrick; Francesca D. Frentiu; Gregor Devine; Laith Yakob; Zhiwei Xu; Zhongjie Li; Weizhong Yang; Wenbiao Hu (International Journal of Biometeorology, 2021)

International Quality-Controlled Ocean Database (IQuOD) v0.1: The Temperature Uncertainty Specification - Rebecca Cowley; Rachel E. Killick; Tim Boyer; Viktor Gouretski; Franco Reseghetti; Shoichi Kizu; Matthew D. Palmer; Lijing Cheng; Andrea Storto; Marc Le Menn; Simona Simoncelli; Alison M. Macdonald; et al. (Frontiers in Marine Science, 2021)
Ocean temperature observations are crucial for a host of climate research and forecasting activities, such as climate monitoring, ocean reanalysis and state estimation, seasonal-to-decadal forecasts, and ocean forecasting. For all of these applications, it is crucial to understand the uncertainty attached to each of the observations, accounting for changes in instrument technology and observing practices over time. Here, we describe the rationale behind the uncertainty specification provided for all in situ ocean temperature observations in the International Quality-controlled Ocean Database (IQuOD) v0.1, a value-added data product served alongside the World Ocean Database (WOD). We collected information from manufacturer specifications and other publications, providing the end user with uncertainty estimates based mainly on instrument type, along with extant auxiliary information such as calibration and collection method. The provision of a consistent set of observation uncertainties will provide a more complete understanding of historical ocean observations used to examine the changing environment. Moving forward, IQuOD will continue to work with the ocean observation, data assimilation and ocean climate communities to further refine uncertainty quantification. We encourage submissions of metadata and information about historical practices to the IQuOD project and WOD.

Novel disease resistance gene paralogs created by CRISPR/Cas9 in soy - Ervin D. Nagy; Julia L. Stevens; Neil Yu; Chris S. Hubmeier; Nona LaFaver; Megan Gillespie; Brian Gardunia; Qianshun Cheng; Steven Johnson; Audrey L. Vaughn; Miguel E. Vega-Sanchez; Mingqui Deng; et al. (Plant Cell Reports, 2021)
Key message Novel disease resistance gene paralogues are generated by targeted chromosome cleavage of tandem duplicated NBS-LRR gene complexes and subsequent DNA repair in soybean. This study demonstrates accelerated diversification of innate immunity of plants using CRISPR. Abstract Nucleotide-binding-site-leucine-rich-repeat (NBS-LRR) gene families are key components of effector-triggered immunity. They are often arranged in tandem duplicated arrays in the genome, a configuration that is conducive to recombinations that will lead to new, chimeric genes. These rearrangements have been recognized as major sources of novel disease resistance phenotypes. Targeted chromosome cleavage by CRISPR/Cas9 can conceivably induce rearrangements and thus emergence of new resistance gene paralogues. Two NBS-LRR families of soy have been selected to demonstrate this concept: a four-copy family in the Rpp1 region (Rpp1L) and a large, complex locus, Rps1 with 22 copies. Copy-number variations suggesting large-scale, CRISPR/Cas9-mediated chromosome rearrangements in the Rpp1L and Rps1 complexes were detected in up to 58.8% of progenies of primary transformants using droplet-digital PCR. Sequencing confirmed development of novel, chimeric paralogs with intact open reading frames. These novel paralogs may confer new disease resistance specificities. This method to diversify innate immunity of plants by genome editing is readily applicable to other disease resistance genes or other repetitive loci.

Brain activation and connectivity in anorexia nervosa and body dysmorphic disorder when viewing bodies: relationships to clinical symptoms and perception of appearance - Teena D. Moody; Francesca Morfini; Gigi Cheng; Courtney L. Sheen; Wesley T Kerr; Michael Strober; Jamie D. Feusner (Brain Imaging and Behavior, 2021)

Global transcriptomic profiles of circulating leucocytes in early lactation cows with clinical or subclinical mastitis - Zhangrui Cheng; Laura Buggiotti; Mazdak Salavati; Cinzia Marchitelli; Sergio Palma-Vera; Alistair Wylie; Haruko Takeda; Lijing Tang; Mark A. Crowe; D. Claire Wathes; Mark Crowe; Niamh McLoughlin; et al. (Molecular Biology Reports, 2021)

Development of vaccine formulations: past, present, and future - Carmine D’Amico; Flavia Fontana; Ruoyu Cheng; Hélder A. Santos (Drug Delivery and Translational Research, 2021)
The current situation, heavily influenced by the ongoing pandemic, puts vaccines back into the spotlight. However, the conventional and traditional vaccines present disadvantages, particularly related to immunogenicity, stability, and storage of the final product. Often, such products require the maintenance of a “cold chain,” impacting the costs, the availability, and the distribution of vaccines. Here, after a recall of the mode of action of vaccines and the types of vaccines currently available, we analyze the past, present, and future of vaccine formulation. The past focuses on conventional formulations, the present discusses the use of nanoparticles for vaccine delivery and as adjuvants, while the future presents microneedle patches as alternative formulation and administration route. Finally, we compare the advantages and disadvantages of injectable solutions, nanovaccines, and microneedles in terms of efficacy, stability, and patient-friendly design. Graphical abstract Different approaches to vaccine formulation development, the conventional vaccine formulations from the past, the current development of lipid nanoparticles as vaccines, and the near future microneedles formulations are discussed in this review.

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

Neuronal Protein Farnesylation Regulates Hippocampal Synaptic Plasticity and Cognitive Function - Wenhui Qu; Kiall F. Suazo; Wenfeng Liu; Shaowu Cheng; Angela Jeong; David Hottman; Li-Lian Yuan; Mark D. Distefano; Ling Li (Molecular Neurobiology, 2021)

Calcium sensitivity during staircase with sequential incompletely fused contractions - Lisa D. Glass; Arthur J. Cheng; Brian R. MacIntosh (Journal of Muscle Research and Cell Motility, 2021)

Identification of hybrid green peafowl using mitochondrial and nuclear markers - Han Yu Du; Xin Yuan Zhang; Thi Dao Dinh; Yue Ma; Cheng Zong; Guang Long Li; Thomas D. Dahmer; Yan Chun Xu (Conservation Genetics Resources, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Stable isotopes reveal effects of natural drivers and anthropogenic pressures on isotopic niches of invertebrate communities in a large subtropical river of China - Sai Wang; Lin-Hui Su; Bang-Ke Luo; Ying-Jun Qin; Simon D. Stewart; Jin-Peng Tang; Tuan-Tuan Wang; Yang Yang; Gong Cheng (Environmental Science and Pollution Research, 2020)

An investigation of the relationship between glutamate and resting state connectivity in chronic cannabis users - Sharlene D. Newman; Hu Cheng; Dae-Jin Kim; Ashley Schnakenberg-Martin; Ulrike Dydak; Shalmali Dharmadhikari; William Hetrick; Brian O’Donnell (Brain Imaging and Behavior, 2020)

An energy budget model for estimating the thermal comfort of children - Wenwen Cheng; Robert D. Brown (International Journal of Biometeorology, 2020)

Testicular cancer in Hispanics: incidence of subtypes over time according to neighborhood sociodemographic factors in California - Mindy C. DeRouen; Meg McKinley; Sumit Anil Shah; Hala T. Borno; Rhonda Aoki; Daphne Y. Lichtensztajn; John T. Leppert; James D. Brooks; Benjamin I. Chung; Scarlett Lin Gomez; Iona Cheng (Cancer Causes & Control, 2020)

Impact of Climate Change on Wintering Ground of Japanese Anchovy (Engraulis japonicus) Using Marine Geospatial Statistics - Shuhao Liu; Yang Liu; Irene D. Alabia; Yongjun Tian; Zhenjiang Ye; Haiqing Yu; Jianchao Li; Jiahua Cheng (Frontiers in Marine Science, 2020)

Creating a space for place and multidimensional well-being: lessons learned from localizing the SDGs - Eleanor J. Sterling; Puaʻala Pascua; Amanda Sigouin; Nadav Gazit; Lisa Mandle; Erin Betley; John Aini; Simon Albert; Sophie Caillon; Jennifer E. Caselle; Samantha H. Cheng; Joachim Claudet; et al. (Sustainability Science, 2020)
Achieving sustainable development globally requires multilevel and interdisciplinary efforts and perspectives. Global goals shape priorities and actions at multiple scales, creating cascading impacts realized at the local level through the direction of financial resources and implementation of programs intended to achieve progress towards these metrics. We explore ways to localize global goals to best support human well-being and environmental health by systematically comparing the UN Sustainable Development Goals (SDGs) with regionally-derived well-being dimensions that encompass components of social–ecological resilience across the Pacific Islands. Our research shows that, in the context of the Pacific, there are overlaps but also significant gaps between regional conceptions of well-being and the globally-derived SDGs. Some dimensions, related to human health and access to infrastructure and finances, are well represented in the SDGs. Other dimensions of high importance when localizing perspectives of well-being, such as those regarding connections between and across people and place and Indigenous and local knowledge, are not. Furthermore, internationally generated indicators may result in trade-offs and measurement challenges in local contexts. Creating space for place-based values in global sustainability planning aligns with international calls for transformational changes needed to achieve global goals. We identify challenges in applying SDG indicators at the local level and provide lessons learned to foster equitable and holistic approaches and outcomes for sustainability.

Great journey of Great Tits (Parus major group): Origin, diversification and historical demographics of a broadly distributed bird lineage - Gang Song; Ruiying Zhang; Fernando Machado‐Stredel; Per Alström; Ulf S. Johansson; Martin Irestedt; Herman L. Mays; Bailey D. McKay; Isao Nishiumi; Yalin Cheng; Yanhua Qu; Per G. P. Ericson; et al. (Journal of Biogeography, 2020)
Aim The Pleistocene glacial cycles play a prominent role in shaping phylogeographical patterns of organisms, while few studies have focused on the regional difference of glacial effects. By acquiring comprehensive knowledge of the origin, diversification and historical demography of an intensively studied passerine species complex, Great Tit, we aim to test the regional variation of the Late Pleistocene glaciation impacts on this widely distributed bird lineage. Location Eurasia and associated peninsulas and archipelagos. Taxa Parus major species complex. Methods Phylogeny, divergence times and demographic dynamics were estimated with Bayesian methods. Population structure, genetic diversity and correlation between genetic and physical distances were estimated based on mtDNA variation. Glacial‐to‐present distributional changes were assessed via ecological niche modelling (ENM). Results Five major clades (Central Asia, Eastern Asia, Eastern Himalaya, Northern and Western Eurasia and Southern Asia) were detected, with divergence times ranging 1.57–0.50 million years ago. Genetic diversity values and Bayesian skyline plots suggest that the three eastern clades had a deeper population history. A more complex geographic structure was observed in East Asia. Demographic expansion during the last glacial cycle was indicated for all five clades. ENM results showed broad conservatism of traits related to climate tolerances, and generally broader and more continuous distributional patterns under glacial conditions. Main Conclusions The Great Tit complex probably originated in Southeast Asia. Geographic barriers, such as the deserts of Central Asia and the Qinghai–Tibet Plateau appear to be related to the lineage divergence. Late Pleistocene climate cycles influenced both demographic dynamics and divergence, especially in terms of east–west differences in relation to geographic complexity.

Lactobacillus plantarum USM8613 Aids in Wound Healing and Suppresses Staphylococcus aureus Infection at Wound Sites - Jia Sin Ong; Todd D. Taylor; Cheng Chung Yong; Boon Yin Khoo; Sreenivasan Sasidharan; Sy Bing Choi; Hiroshi Ohno; Min Tze Liong (Probiotics and Antimicrobial Proteins, 2020)

High ecosystem multifunctionality under moderate grazing is associated with high plant but low bacterial diversity in a semi-arid steppe grassland - Xinyu Wang; Frank Yonghong Li; Yanan Wang; Xinmin Liu; Jianwei Cheng; Junzhen Zhang; Taogetao Baoyin; Richard D. Bardgett (Plant and Soil, 2020)

Effects of seasonal upwelling and runoff on water chemistry and growth and survival of native and commercial oysters - Jordan A. Hollarsmith; Jason S. Sadowski; Manon M. M. Picard; Brian Cheng; James Farlin; Ann Russell; Edwin D. Grosholz (Limnology and Oceanography, 2020)
The effects of climate change, including ocean acidification and ocean heatwaves, on biological communities in estuaries are often uncertain. Part of the uncertainty is due to the complex suite of environmental factors in addition to acidification and warming that influence the growth of shells and skeletons of many estuarine organisms. The goal of this study was to document spatial and temporal variation in water column properties and to measure the in situ effects on larval and recently settled stages of ecologically important Olympia oysters ( Ostrea lurida ) and commercially important Pacific oysters ( Crassostrea gigas ) in a low‐inflow estuary with a Mediterranean climate in Northern California. Our results reveal that seasonal inputs of upwelled or riverine water create important and predictable gradients of carbonate system parameters, temperature, salinity, dissolved oxygen (DO), and other variables that influence oyster performance, and that the influence of these gradients is contingent upon the location in the estuary as well as seasonal timing. During upwelling events (dry season), temperature, carbonate chemistry, and DO had the greatest impact on oyster performance. During runoff events (wet season), gradients in salinity, nutrient concentrations, and total alkalinity driven by river discharge were comparatively more important. These results suggest that the spatial importance of carbonate chemistry and temperature are seasonally variable and are two of several other factors that determine oyster performance. We use these results to discuss future impacts on oysters given projected regional changes in the frequency and magnitude of upwelling and precipitation‐driven runoff events.

Reconciliation of discrepant U–Pb, Lu–Hf, Sm–Nd, Ar–Ar and U–Th/He dates in an amphibolite from the Cathaysia Block in Southern China - Hao Cheng; Elias M. Bloch; Evangelos Moulas; Jeffrey D. Vervoort (Contributions to Mineralogy and Petrology, 2020)

Consensus Paper: Experimental Neurostimulation of the Cerebellum - Lauren N. Miterko; Kenneth B. Baker; Jaclyn Beckinghausen; Lynley V. Bradnam; Michelle Y. Cheng; Jessica Cooperrider; Mahlon R. DeLong; Simona V. Gornati; Mark Hallett; Detlef H. Heck; Freek E. Hoebeek; Abbas Z. Kouzani; et al. (The Cerebellum, 2019)

A comparison of regional brain volumes and white matter connectivity in subjects with stimulant induced psychosis versus schizophrenia - Peter D. Alexander; Kristina M. Gicas; Alex Cheng; Donna J. Lang; Ric M. Procyshyn; Alexandra T. Vertinsky; William J. Panenka; Allen E. Thornton; Alexander Rauscher; Jamie Y. X. Wong; Tasha Chan; Andrea A. Jones; et al. (Psychopharmacology, 2019)

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Molecular characterization of heat shock protein 90 from the dinoflagellate Prorocentrum donghaiense and its transcriptional response to thermal, copper and nutrient stresses - Chun Y. Zhang; Guo F. Chen; Yuan Y. Wang; Xu D. Zhang; Cheng H. Li (Marine Biology Research, 2019)

An End-to-end System for Automatic Characterization of Iba1 Immunopositive Microglia in Whole Slide Imaging - Alexander D. Kyriazis; Shahriar Noroozizadeh; Amir Refaee; Woongcheol Choi; Lap-Tak Chu; Asma Bashir; Wai Hang Cheng; Rachel Zhao; Dhananjay R. Namjoshi; Septimiu E. Salcudean; Cheryl L. Wellington; Guy Nir (Neuroinformatics, 2019)

A modified Sarma method for stability analysis of layered slopes - X. P. Zhou; X. D. Zhao; L. N. Y. Wong; H. Cheng (Bulletin of Engineering Geology and the Environment, 2019)

Baroreflex Control of Heart Rate in Mice Overexpressing Human SOD1: Functional Changes in Central and Vagal Efferent Components - Jin Chen; He Gu; Robert D. Wurster; Zixi Cheng (Neuroscience Bulletin, 2019)

Novel metformin-containing resin promotes odontogenic differentiation and mineral synthesis of dental pulp stem cells - Suping Wang; Yang Xia; Tao Ma; Michael D. Weir; Ke Ren; Mark A. Reynolds; Yan Shu; Lei Cheng; Abraham Schneider; Hockin H. K. Xu (Drug Delivery and Translational Research, 2019)

Amyloid Precursor Protein Dimerisation Reduces Neurite Outgrowth - Luan Luu; Giuseppe D. Ciccotosto; Laura J. Vella; Lesley Cheng; Laila C. Roisman; Gerhard Multhaup; Andrew F. Hill; Lisa-Marie Munter; Roberto Cappai (Molecular Neurobiology, 2019)

Identification of major insect pests of Amaranthus spp. and germplasm screening for insect resistance in Tanzania - Jason D. Smith; Fekadu F. Dinssa; Robert S. Anderson; Fu-cheng Su; Ramasamy Srinivasan (International Journal of Tropical Insect Science, 2018)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Role of Ca2+ in changing active force during intermittent submaximal stimulation in intact, single mouse muscle fibers - Lisa D. Glass; Arthur J. Cheng; Brian R. MacIntosh (Pflügers Archiv - European Journal of Physiology, 2018)

Using machine learning to advance synthesis and use of conservation and environmental evidence - S.H. Cheng; C. Augustin; A. Bethel; D. Gill; S. Anzaroot; J. Brun; B. DeWilde; R.C. Minnich; R. Garside; Y.J. Masuda; D.C. Miller; D. Wilkie; et al. (Conservation Biology, 2018)
Article impact statement : Machine learning optimizes processes of systematic evidence synthesis and improves its utility for evidence‐based conservation.

The association between smoking cessation before and after diagnosis and non-muscle-invasive bladder cancer recurrence: a prospective cohort study - Frits H. M. van Osch; Sylvia H. J. Jochems; Raoul C. Reulen; Sarah J. Pirrie; Duncan Nekeman; Anke Wesselius; Nicholas D. James; D. Michael A. Wallace; K. K. Cheng; Frederik J. van Schooten; Richard T. Bryan; Maurice P. Zeegers (Cancer Causes & Control, 2018)

Fruit and vegetable intake and the risk of recurrence in patients with non-muscle invasive bladder cancer: a prospective cohort study - Sylvia H. J. Jochems; Frits H. M. van Osch; Raoul C. Reulen; Mitch van Hensbergen; Duncan Nekeman; Sarah Pirrie; Anke Wesselius; Frederik-Jan van Schooten; Nicholas D. James; D. Michael A. Wallace; Richard T. Bryan; K. K. Cheng; et al. (Cancer Causes & Control, 2018)

The coronafacoyl phytotoxins: structure, biosynthesis, regulation and biological activities - Dawn R. D. Bignell; Zhenlong Cheng; Luke Bown (Antonie van Leeuwenhoek, 2018)

Extraction of Parkinson’s Disease-Related Features from Local Field Potentials for Adaptive Deep Brain Stimulation - D. Zhao; Q. Sun; S. Cheng; M. He; X. Chen; X. Hou (Neurophysiology, 2018)

Noninvasive induction of angiogenesis in tissues by external suction: sequential optimization for use in reconstructive surgery - G. Giatsidis; L. Cheng; Anthony Haddad; K. Ji; J. Succar; L. Lancerotto; J. Lujan-Hernandez; P. Fiorina; H. Matsumine; D. P. Orgill (Angiogenesis, 2018)

The effects of scatter-hoarding rodents on Mongolian oak (Quercus mongolica) acorn dispersal and seedling distribution in urban woodland - H. Hao; C. Jiang; Jianping Wu; Cheng Zong; D. Zeng; N. Alimubike (Urban Ecosystems, 2017)

Untangling the proximate causes and underlying drivers of deforestation and forest degradation in Myanmar - Cheng Ling Lim; Graham W. Prescott; Jose Don T. De Alban; Alan D. Ziegler; Edward L. Webb (Conservation Biology, 2017)
Political transitions often trigger substantial environmental changes. In particular, deforestation can result from the complex interplay among the components of a system—actors, institutions, and existing policies—adapting to new opportunities. A dynamic conceptual map of system components is particularly useful for systems in which multiple actors, each with different worldviews and motivations, may be simultaneously trying to alter different facets of the system, unaware of the impacts on other components. In Myanmar, a global biodiversity hotspot with the largest forest area in mainland Southeast Asia, ongoing political and economic reforms are likely to change the dynamics of deforestation drivers. A fundamental conceptual map of these dynamics is therefore a prerequisite for interventions to reduce deforestation. We used a system‐dynamics approach and causal‐network analysis to determine the proximate causes and underlying drivers of forest loss and degradation in Myanmar from 1995 to 2016 and to articulate the linkages among them. Proximate causes included infrastructure development, timber extraction, and agricultural expansion. These were stimulated primarily by formal agricultural, logging, mining, and hydropower concessions and economic investment and social issues relating to civil war and land tenure. Reform of land laws, the link between natural resource extraction and civil war, and the allocation of agricultural concessions will influence the extent of future forest loss and degradation in Myanmar. The causal‐network analysis identified priority areas for policy interventions, for example, creating a public registry of land‐concession holders to deter corruption in concession allocation. We recommend application of this analytical approach to other countries, particularly those undergoing political transition, to inform policy interventions to reduce forest loss and degradation.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Timing of stressors alters interactive effects on a coastal foundation species - Jillian M. Bible; Brian S. Cheng; Andrew L. Chang; Matthew C. Ferner; Kerstin Wasson; Chela J. Zabin; Marilyn Latta; Eric Sanford; Anna Deck; Edwin D. Grosholz (Ecology, 2017)
The effects of climate‐driven stressors on organismal performance and ecosystem functioning have been investigated across many systems; however, manipulative experiments generally apply stressors as constant and simultaneous treatments, rather than accurately reflecting temporal patterns in the natural environment. Here, we assessed the effects of temporal patterns of high aerial temperature and low salinity on survival of Olympia oysters ( Ostrea lurida ), a foundation species of conservation and restoration concern. As single stressors, low salinity (5 and 10 psu) and the highest air temperature (40°C) resulted in oyster mortality of 55.8, 11.3, and 23.5%, respectively. When applied on the same day, low salinity and high air temperature had synergistic negative effects that increased oyster mortality. This was true even for stressor levels that were relatively mild when applied alone (10 psu and 35°C). However, recovery times of two or four weeks between stressors eliminated the synergistic effects. Given that most natural systems threatened by climate change are subject to multiple stressors that vary in the timing of their occurrence, our results suggest that it is important to examine temporal variation of stressors in order to more accurately understand the possible biological responses to global change.

Laser Sintered Porous Ti–6Al–4V Implants Stimulate Vertical Bone Growth - Alice Cheng; David J. Cohen; Adrian Kahn; Ryan M. Clohessy; Kaan Sahingur; Joseph B. Newton; Sharon L. Hyzy; Barbara D. Boyan; Zvi Schwartz (Annals of Biomedical Engineering, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

Genetic mapping and haplotype analysis of a locus for quantitative resistance to Fusarium graminearum in soybean accession PI 567516C - Peng Cheng; Cassidy R. Gedling; Gunvant Patil; Tri D. Vuong; J. Grover Shannon; Anne E. Dorrance; Henry T. Nguyen (Theoretical and Applied Genetics, 2017)

Morphological assessment of the Octopus vulgaris species complex evaluated in light of molecular‐based phylogenetic inferences - Michael D. Amor; Mark D. Norman; Alvaro Roura; Tatiana S. Leite; Ian G. Gleadall; Amanda Reid; Catalina Perales‐Raya; Chung‐Cheng Lu; Colin J. Silvey; Erica A. G. Vidal; Frederick G. Hochberg; Xiaodong Zheng; et al. (Zoologica Scripta, 2017)
Cryptic species are common in the ocean, particularly among marine invertebrates such as octopuses. Delineating cryptic species is particularly problematic in octopus taxonomy where the plasticity recorded among taxonomic characters often results in low resolution at the species level. This study investigated the morphological relationships among seven phylogenetic clades (identified using cytochrome c oxidase subunit I) of the broadly distributed Octopus vulgaris species complex and close relatives. Morphological analyses in this study were successful in delimiting O. sinensis , Brazilian O . vulgaris and O. vulgaris sensu stricto , which was congruent with the molecular findings of this study. Analyses based on male morphology were successful in distinguishing 14 of 15 total pairwise comparisons and proved to be a more reliable indicator of species‐level relationships in comparison with female morphology. The majority of characters with the greatest discriminatory power were male sexual traits. Significant morphological differences were also recorded among sampling localities of conspecifics, with phenotype showing correlation with local environmental data. The findings of this study support the hypothesis that multiple O. vulgaris ‐like species are currently being incorrectly treated under a single species name, O. vulgaris . Octopuses being exported globally under the name O. vulgaris are of extremely high fisheries market value and profile. Our findings have potentially significant implications for the naming and conservation of commercially harvested members of this species complex throughout their ranges.

Evaluation of Aphis glycines as an Alternative Host for Supporting Aphelinus albipodus Against Myzus persicae on Capsicum annuum cv. Ox Horn and Hejiao 13 - Y Q Song; H Z Sun; J Du; X D Wang; Z J Cheng (Neotropical Entomology, 2017)

Dalbavancin reduces biofilms of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE) - D. Knafl; S. Tobudic; S. C. Cheng; D. R. Bellamy; F. Thalhammer (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

The Effect of Substrate Stiffness on Cardiomyocyte Action Potentials - Sean D. Boothe; Jackson D. Myers; Seokwon Pok; Junping Sun; Yutao Xi; Raymond M Nieto; Jie Cheng; Jeffrey G. Jacot (Cell Biochemistry and Biophysics, 2016)

Observed and simulated full-depth ocean heat-content changes for 1970–2005 - Lijing Cheng; Kevin E. Trenberth; Matthew D. Palmer; Jiang Zhu; John P. Abraham (Ocean Science, 2016)
Greenhouse-gas emissions have created a planetary energy imbalance that is primarily manifested by increasing ocean heat content (OHC). Updated observational estimates of full-depth OHC change since 1970 are presented that account for recent advancements in reducing observation errors and biases. The full-depth OHC has increased by 0.74 [0.68, 0.80] × 1022 J yr−1 (0.46 Wm−2) and 1.22 [1.16–1.29] × 1022 J yr−1 (0.75 Wm−2) for 1970–2005 and 1992–2005, respectively, with a 5 to 95 % confidence interval of the median. The CMIP5 models show large spread in OHC changes, suggesting that some models are not state-of-the-art and require further improvements. However, the ensemble median has excellent agreement with our observational estimate: 0.68 [0.54–0.82] × 1022 J yr−1 (0.42 Wm−2) from 1970 to 2005 and 1.25 [1.10–1.41] × 1022 J yr−1 (0.77 Wm−2) from 1992 to 2005. These results increase confidence in both the observational and model estimates to quantify and study changes in Earth's energy imbalance over the historical period. We suggest that OHC be a fundamental metric for climate model validation and evaluation, especially for forced changes (decadal timescales).

Mitigation of multipath effect in GNSS short baseline positioning by the multipath hemispherical map - D. Dong; M. Wang; W. Chen; Z. Zeng; L. Song; Q. Zhang; M. Cai; Y. Cheng; J. Lv (Journal of Geodesy, 2016)

A novel soil manganese mechanism drives plant species loss with increased nitrogen deposition in a temperate steppe - Qiuying Tian; Nana Liu; Wenming Bai; Linghao Li; Jiquan Chen; Peter B. Reich; Qiang Yu; Dali Guo; Melinda D. Smith; Alan K. Knapp; Weixin Cheng; Peng Lu; et al. (Ecology, 2016)
Loss of plant diversity with increased anthropogenic nitrogen (N) deposition in grasslands has occurred globally. In most cases, competitive exclusion driven by preemption of light or space is invoked as a key mechanism. Here, we provide evidence from a 9‐yr N‐addition experiment for an alternative mechanism: differential sensitivity of forbs and grasses to increased soil manganese (Mn) levels. In Inner Mongolia steppes, increasing the N supply shifted plant community composition from grass–forb codominance (primarily Stipa krylovii and Artemisia frigida , respectively) to exclusive dominance by grass, with associated declines in overall species richness. Reduced abundance of forbs was linked to soil acidification that increased mobilization of soil Mn, with a 10‐fold greater accumulation of Mn in forbs than in grasses. The enhanced accumulation of Mn in forbs was correlated with reduced photosynthetic rates and growth, and is consistent with the loss of forb species. Differential accumulation of Mn between forbs and grasses can be linked to fundamental differences between dicots and monocots in the biochemical pathways regulating metal transport. These findings provide a mechanistic explanation for N‐induced species loss in temperate grasslands by linking metal mobilization in soil to differential metal acquisition and impacts on key functional groups in these ecosystems.

White matter abnormalities of microstructure and physiological noise in schizophrenia - Hu Cheng; Sharlene D. Newman; Jerillyn S. Kent; Amanda Bolbecker; Mallory J. Klaunig; Brian F. O’Donnell; Aina Puce; William P. Hetrick (Brain Imaging and Behavior, 2015)

Speciation processes in putative island endemic sister bat species: false impressions from mitochondrial DNA and microsatellite data - Hao‐Chih Kuo; Shiang‐Fan Chen; Yin‐Ping Fang; James A. Cotton; Joe D. Parker; Gábor Csorba; Burton K. Lim; Judith L. Eger; Chia‐Hong Chen; Cheng‐Han Chou; Stephen J. Rossiter (Molecular Ecology, 2015)
Cases of geographically restricted co‐occurring sister taxa are rare and may point to potential divergence with gene flow. The two bat species Murina gracilis and Murina recondita are both endemic to Taiwan and are putative sister species. To test for nonallopatric divergence and gene flow in these taxa, we generated sequences using Sanger and next‐generation sequencing, and combined these with microsatellite data for coalescent‐based analyses. Mt DNA phylogenies supported the reciprocally monophyletic sister relationship between M. gracilis and M. recondita ; however, clustering of microsatellite genotypes revealed several cases of species admixture suggesting possible introgression. Sequencing of microsatellite flanking regions revealed that admixture signatures stemmed from microsatellite allele homoplasy rather than recent introgressive hybridization, and also uncovered an unexpected sister relationship between M. recondita and the continental species Murina eleryi , to the exclusion of M. gracilis . To dissect the basis of these conflicts between nc DNA and mt DNA , we analysed sequences from 10 anonymous nc DNA loci with * beast and isolation‐with‐migration and found two distinct clades of M. eleryi , one of which was sister to M. recondita . We conclude that Taiwan was colonized by the ancestor of M. gracilis first, followed by the ancestor of M. recondita after a period of allopatric divergence. After colonization, the mitochondrial genome of M. recondita was replaced by that of the resident M. gracilis . This study illustrates how apparent signatures of sympatric divergence can arise from complex histories of allopatric divergence, colonization and hybridization, thus highlighting the need for rigorous analyses to distinguish between such scenarios.

Nasopharyngeal carriage and macrolide resistance in Indigenous children with bronchiectasis randomized to long-term azithromycin or placebo - K. M. Hare; K. Grimwood; A. B. Chang; M. D. Chatfield; P. C. Valery; A. J. Leach; H. C. Smith-Vaughan; P. S. Morris; C. A. Byrnes; P. J. Torzillo; A. C. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Global diversity and taxonomy of the Auricularia auricula-judae complex (Auriculariales, Basidiomycota) - Fang Wu; Yuan Yuan; Shuang-Hui He; Asanka R. Bandara; Kevin D. Hyde; Vera F. Malysheva; De-Wei Li; Yu-Cheng Dai (Mycological Progress, 2015)

Diaporthe rostrata, a novel ascomycete from Juglans mandshurica associated with walnut dieback - Xin-Lei Fan; Kevin D. Hyde; Dhanushka Udayanga; Xing-Yu Wu; Cheng-Ming Tian (Mycological Progress, 2015)

Chemicals to induce plastid signals in Arabidopsis seedlings - Z.-W. Zhang; F. Wu; J. Cheng; M. Yuan; Y.-E. Chen; D.-W. Zhang; F. Zhu; S. Yuan (Plant Biosystems, 2015)

Mercury Exposure and Heart Rate Variability: a Systematic Review - Matthew O. Gribble; Alan Cheng; Ronald D. Berger; Lori Rosman; Eliseo Guallar (Current Environmental Health Reports, 2015)

Dynamics of the worldwide number of fungi with emphasis on fungal diversity in China - Yu-Cheng Dai; Bao-Kai Cui; Jing Si; Shuang-Hui He; Kevin D. Hyde; Hai-Sheng Yuan; Xiao-Yong Liu; Li-Wei Zhou (Mycological Progress, 2015)

A comparison of paediatric and adult infectious diseases consultations in Australia and New Zealand - C. C. Blyth; T. Walls; A. C. Cheng; R. J. Murray; D. A. Fisher; P. R. Ingram; J. S. Davis (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Assessment of toxicity and coagulopathy of brodifacoum in Japanese quail and testing in wild owls - Kirstin H. Webster; Kendal E. Harr; Darin C. Bennett; Tony D. Williams; Kimberly M. Cheng; France Maisonneuve; John E. Elliott (Ecotoxicology, 2015)

Assessing the genetic diversity and resistance to Cucumber mosaic virus and Tobacco etch virus of tobacco cultivars in China - W. Chen; Z. P. Luo; W. T. Liu; H. Liu; D. F. Ma; J. H. Snyder; X. Li; T. Huang; J. L. Cheng; X. Xie; Y. F. Wu (Australasian Plant Pathology, 2015)

Testing local and global stressor impacts on a coastal foundation species using an ecologically realistic framework - Brian S. Cheng; Jillian M. Bible; Andrew L. Chang; Matthew C. Ferner; Kerstin Wasson; Chela J. Zabin; Marilyn Latta; Anna Deck; Anne E. Todgham; Edwin D. Grosholz (Global Change Biology, 2015)
Despite the abundance of literature on organismal responses to multiple environmental stressors, most studies have not matched the timing of experimental manipulations with the temporal pattern of stressors in nature. We test the interactive effects of diel‐cycling hypoxia with both warming and decreased salinities using ecologically realistic exposures. Surprisingly, we found no evidence of negative synergistic effects on Olympia oyster growth; rather, we found only additive and opposing effects of hypoxia (detrimental) and warming (beneficial). We suspect that diel‐cycling provided a temporal refuge that allowed physiological compensation. We also tested for latent effects of warming and hypoxia to low‐salinity tolerance using a seasonal delay between stressor events. However, we did not find a latent effect, rather a threshold survival response to low salinity that was independent of early life‐history exposure to warming or hypoxia. The absence of synergism is likely the result of stressor treatments that mirror the natural timing of environmental stressors. We provide environmental context for laboratory experimental data by examining field time series environmental data from four North American west coast estuaries and find heterogeneous environmental signals that characterize each estuary, suggesting that the potential stressor exposure to oysters will drastically differ over moderate spatial scales. This heterogeneity implies that efforts to conserve and restore oysters will require an adaptive approach that incorporates knowledge of local conditions. We conclude that studies of multiple environmental stressors can be greatly improved by integrating ecologically realistic exposure and timing of stressors found in nature with organismal life‐history traits.

Group 16SrXII phytoplasma strains, including subgroup 16SrXII-E (‘Candidatus Phytoplasma fragariae’) and a new subgroup, 16SrXII-I, are associated with diseased potatoes (Solanum tuberosum) in the Yunnan and Inner Mongolia regions of China - Mingyuan Cheng; Jiahong Dong; Ing-Ming Lee; Kristi D. Bottner-Parker; Yan Zhao; Robert E. Davis; Paul J. Laski; Zhongkai Zhang; Jenifer Huang McBeath (European Journal of Plant Pathology, 2015)

Mechanistic relationships between hepatic genotoxicity and carcinogenicity in male B6C3F1 mice treated with polycyclic aromatic hydrocarbon mixtures - Tracie D. Phillips; Molly Richardson; Yi-Shing Lisa Cheng; Lingyu He; Thomas J. McDonald; Leslie H. Cizmas; Stephen H. Safe; Kirby C. Donnelly; Fen Wang; Bhagavatula Moorthy; Guo-Dong Zhou (Archives of Toxicology, 2015)

The RIG-I-like helicase receptor MDA5 (IFIH1) is involved in the host defense against Candida infections - M. Jaeger; R. van der Lee; S.-C. Cheng; M. D. Johnson; V. Kumar; A. Ng; T. S. Plantinga; S. P. Smeekens; M. Oosting; X. Wang; W. Barchet; K. Fitzgerald; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Mapping QTLs of caudal fin length in common carp ( Cyprinus carpio L.) - C Lu; Y Zhang; X Zheng; X Zhang; C Li; Y Kuang; D Cao; L Cheng; G Qiu; X Sun (New Zealand Journal of Marine and Freshwater Research, 2015)
Common carp ( Cyprinus carpio L.) exhibits significant morphological variability in the shape and size of the caudal fin. In this study, we used 190 progeny from two F 1 parents to identify and map quantitative trait loci (QTLs) that influence caudal fin length ( CFL ) and the ratio ( RCS ) between caudal fin length and standard length ( SL ) based on a microsatellite genetic map of common carp. A total of 15 QTLs were detected in seven different linkage groups. One significant and eight suggestive QTLs affecting CFL were identified on LG8, LG14, LG29, LG32 and LG44, which explained 8.0%–22.1% of the phenotypic variation; six suggestive QTLs affecting RCS were detected on LG8, LG32, LG46 and LG48, which explained 7.0%–15.4% of the phenotypic variation. The QTLs for caudal fin length detected in this study may serve as a starting point for identification of genes involved in caudal fin development in common carp.

Effects of water quality of the basin caused by nitrogen loss from soil in drought - B. B. Huang; D. H. Yan; H. Wang; B. F. Cheng; X. H. Cui (Natural Hazards, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Alterations of digestive enzyme activities, intestinal morphology and microbiota in juvenile paddlefish, Polyodon spathula, fed dietary probiotics - Cheng Fang; Mingyang Ma; Hong Ji; Tongjun Ren; Steven D. Mims (Fish Physiology and Biochemistry, 2015)

Anisotropic Analysis of I-Walls in New Orleans - Sudarshan Adhikari; Chung R. Song; Alexander H.-D. Cheng (Marine Georesources & Geotechnology, 2015)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Molecular mapping of genes Yr64 and Yr65 for stripe rust resistance in hexaploid derivatives of durum wheat accessions PI 331260 and PI 480016 - P. Cheng; L. S. Xu; M. N. Wang; D. R. See; X. M. Chen (Theoretical and Applied Genetics, 2014)

The expression of BTG1 is downregulated in nasopharyngeal carcinoma and possibly associated with tumour metastasis - G. G. Sun; Y. D. Wang; Y. J. Cheng; W. N. Hu (Molecular Biology Reports, 2014)

Potential of a Cyclone Prototype Spacer to Improve In Vitro Dry Powder Delivery - Irene Parisini; Sean J. Cheng; Digby D. Symons; Darragh Murnane (Pharmaceutical Research, 2014)

Genome‐wide single‐generation signatures of local selection in the panmictic E uropean eel - J. M. Pujolar; M. W. Jacobsen; T. D. Als; J. Frydenberg; K. Munch; B. Jónsson; J. B. Jian; L. Cheng; G. E. Maes; L. Bernatchez; M. M. Hansen (Molecular Ecology, 2014)
Next‐generation sequencing and the collection of genome‐wide data allow identifying adaptive variation and footprints of directional selection. Using a large SNP data set from 259 RAD ‐sequenced E uropean eel individuals (glass eels) from eight locations between 34 and 64 o N, we examined the patterns of genome‐wide genetic diversity across locations. We tested for local selection by searching for increased population differentiation using F ST ‐based outlier tests and by testing for significant associations between allele frequencies and environmental variables. The overall low genetic differentiation found ( F ST = 0.0007) indicates that most of the genome is homogenized by gene flow, providing further evidence for genomic panmixia in the E uropean eel. The lack of genetic substructuring was consistent at both nuclear and mitochondrial SNP s. Using an extensive number of diagnostic SNP s, results showed a low occurrence of hybrids between E uropean and A merican eel, mainly limited to Iceland (5.9%), although individuals with signatures of introgression several generations back in time were found in mainland Europe. Despite panmixia, a small set of SNP s showed high genetic differentiation consistent with single‐generation signatures of spatially varying selection acting on glass eels. After screening 50 354 SNP s, a total of 754 potentially locally selected SNP s were identified. Candidate genes for local selection constituted a wide array of functions, including calcium signalling, neuroactive ligand–receptor interaction and circadian rhythm. Remarkably, one of the candidate genes identified is PERIOD , possibly related to differences in local photoperiod associated with the >30° difference in latitude between locations. Genes under selection were spread across the genome, and there were no large regions of increased differentiation as expected when selection occurs within just a single generation due to panmixia. This supports the conclusion that most of the genome is homogenized by gene flow that removes any effects of diversifying selection from each new generation.

Cryptic ecology among host generalist Campylobacter jejuni in domestic animals - Samuel K. Sheppard; Lu Cheng; Guillaume Méric; Caroline P. A. de Haan; Ann‐Katrin Llarena; Pekka Marttinen; Ana Vidal; Anne Ridley; Felicity Clifton‐Hadley; Thomas R. Connor; Norval J. C. Strachan; Ken Forbes; et al. (Molecular Ecology, 2014)
Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.

Effects of Androgens on Early Post-ischemic Neurogenesis in Mice - Wenri Zhang; Jian Cheng; Kamila Vagnerova; Yulia Ivashkova; Jennifer Young; Anda Cornea; Marjorie R. Grafe; Stephanie J. Murphy; Patricia D. Hurn; Ansgar M. Brambrink (Translational Stroke Research, 2014)

Atmospheric emission inventory of cadmium from anthropogenic sources - K. Cheng; H. Z. Tian; D. Zhao; L. Lu; Y. Wang; J. Chen; X. G. Liu; W. X. Jia; Z. Huang (International Journal of Environmental Science and Technology, 2014)

Quantifying soil health and tomato crop productivity in urban community and market gardens - J. Reeves; Z. Cheng; J. Kovach; M. D. Kleinhenz; P. S. Grewal (Urban Ecosystems, 2014)

Influence of Unloading Rate on the Strainburst Characteristics of Beishan Granite Under True-Triaxial Unloading Conditions - X. G. Zhao; J. Wang; M. Cai; C. Cheng; L. K. Ma; R. Su; F. Zhao; D. J. Li (Rock Mechanics and Rock Engineering, 2014)

Peginterferon plus Chinese herbal therapy is associated with a higher virological response than only peginterferon therapy in chronic hepatitis C - D. Cheng; E. Liu; Y. Li; R. Liu; L. Bai; Y. Chen; Y. Wang; Y. Chu; M. Wu; G. Cheng; S. Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Endothelial-like properties of claudin-low breast cancer cells promote tumor vascular permeability and metastasis - J. Chuck Harrell; Adam D. Pfefferle; Nicole Zalles; Aleix Prat; Cheng Fan; Andrey Khramtsov; Olufunmilayo I. Olopade; Melissa A. Troester; Andrew C. Dudley; Charles M. Perou (Clinical & Experimental Metastasis, 2014)

The association between pro-inflammatory cytokines, regional cerebral metabolism, and cognitive complaints following adjuvant chemotherapy for breast cancer - K. L. Pomykala; P. A. Ganz; J. E. Bower; L. Kwan; S. A. Castellon; S. Mallam; I. Cheng; R. Ahn; E. C. Breen; M. R. Irwin; D. H. S. Silverman (Brain Imaging and Behavior, 2013)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

An empirical comparison of character‐based and coalescent‐based approaches to species delimitation in a young avian complex - Bailey D. McKay; Herman L. Mays; Yuchun Wu; Hui Li; Cheng‐te Yao; Isao Nishiumi; Fasheng Zou (Molecular Ecology, 2013)
The process of discovering species is a fundamental responsibility of systematics. Recently, there has been a growing interest in coalescent‐based methods of species delimitation aimed at objectively identifying species early in the divergence process. However, few empirical studies have compared these new methods with character‐based approaches for discovering species. In this study, we applied both a character‐based and a coalescent‐based approaches to delimit species in a closely related avian complex, the light‐vented/Taiwan bulbul ( P ycnonotus sinensis / P ycnonotus taivanus ). Population aggregation analyses of plumage, mitochondrial and 13 nuclear intron character data sets produced conflicting species hypotheses with plumage data suggesting three species, mitochondrial data suggesting two species, and nuclear intron data suggesting one species. Such conflict is expected among recently diverged species, and by integrating all sources of data, we delimited three species verified with independently congruent character evidence as well as a more weakly supported fourth species identified by a single character. Attempts to validate species hypothesis using B ayesian P hylogenetics and P hylogeography ( BPP ), a coalescent‐based method of species delimitation, revealed several issues that can seemingly affect statistical support for species recognition. We found that θ priors had a dramatic impact on speciation probabilities, with lower values consistently favouring splitting and higher values consistently favouring lumping. More resolved guide trees also resulted in overall higher speciation probabilities. Finally, we found suggestive evidence that BPP is sensitive to the divergent effects of nonrandom mating caused by intraspecific processes such as isolation‐with‐distance, and therefore, BPP may not be a conservative method for delimiting independently evolving population lineages. Based on these concerns, we questioned the reliability of BPP results and based our conclusions about species limits exclusively on character data.

Soil health as a predictor of lettuce productivity and quality: A case study of urban vacant lots - A. Knight; Z. Cheng; S. S. Grewal; K. R. Islam; M. D. Kleinhenz; P. S. Grewal (Urban Ecosystems, 2013)

Explicit knowledge and real-time action control: anticipating a change does not make us respond more quickly - Brendan D. Cameron; Darian T. Cheng; Romeo Chua; Paul van Donkelaar; Gordon Binsted (Experimental Brain Research, 2013)

Staphylococcus aureus bacteraemia: evaluation of the role of transoesophageal echocardiography in identifying clinically unsuspected endocarditis - A. Incani; C. Hair; P. Purnell; D. P. O’Brien; A. C. Cheng; A. Appelbe; E. Athan (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Population structure of Fusarium oxysporum f. sp. radicis-lycopersici in Florida inferred from vegetative compatibility groups and microsatellites - Cheng-Hua Huang; Pamela D. Roberts; Liane R. Gale; Wade H. Elmer; Lawrence E. Datnoff (European Journal of Plant Pathology, 2013)

Distribution and Removal of Silver and Lead in the Nearshore Waters of Western Taiwan - Cheng-Shiuan Lee; Ching-Ling Wei; Liang-Saw Wen; David D.-D. Sheu; Wen-Huei Lee (Estuaries and Coasts, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

The Effect of Individual Differences in Working Memory Capacity on Sentence Comprehension: An fMRI Study - Sharlene D. Newman; Evie Malaia; Roy Seo; Hu Cheng (Brain Topography, 2013)

Depressed calcium-handling proteins due to endoplasmic reticulum stress and apoptosis in the diabetic heart are attenuated by argirein - F. H. Shi; Y. S. Cheng; D. Z. Dai; H. J. Peng; X. D. Cong; Y. Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Biotic resistance in marine environments - David L. Kimbro; Brian S. Cheng; Edwin D. Grosholz (Ecology Letters, 2013)
Biological invasions depend in part on the resistance of native communities. Meta‐analyses of terrestrial experiments demonstrate that native primary producers and herbivores generally resist invasions of primary producers, and that resistance through competition strengthens with native producer diversity. To test the generality of these findings, we conducted a meta‐analysis of marine experiments. We found that native marine producers generally failed to resist producer invasions through competition unless the native community was diverse, and this diversity effect was weaker in marine than in terrestrial systems. In contrast, native consumers equally resisted invasive producers in both ecosystems. Most marine experiments, however, tested invasive consumers and these invasions were resisted more strongly than were producer invasions. Given these differences between ecosystems and between marine trophic levels, we used a model‐selection approach to assess if factors other than the resistance mechanism (i.e. competition vs. consumption) are more important for predicting marine biotic resistance. These results suggest that understanding marine biotic resistance depends on latitude, habitat and invader taxon, in addition to distinguishing between competition with and consumption by native species. By examining biotic resistance within and across ecosystems, our work provides a more complete understanding of the factors that underlie biological invasions.

pyrG is required for maintaining stable cellular uracil level and normal sporulation pattern under excess uracil stress in Aspergillus nidulans - XianYun Sun; JuFen Zhu; Li Bao; ChengCheng Hu; Cheng Jin; Steven D. Harris; HongWei Liu; ShaoJie Li (Science China Life Sciences, 2013)

The integration of nautical charts to reconstruct 3D harbor area models and apply assisted navigation - Dong-Taur Su; D. C. Lo; Cheng-Wu Chen; Yi-Chang Huang (Natural Hazards, 2013)

Investigation of transferability of BovineSNP50 BeadChip from cattle to water buffalo for genome wide association study - Jun Jing Wu; Li Jun Song; Fang Jie Wu; Xian Wei Liang; Bing Zhuang Yang; D. Claire Wathes; Geoff E. Pollott; Zhangrui Cheng; De Shun Shi; Qing You Liu; Li Guo Yang; Shu Jun Zhang (Molecular Biology Reports, 2013)

Erratum to: Development, Validation, and Application of a Parametric Pediatric Head Finite Element Model for Impact Simulations - Zhigang Li; Jingwen Hu; Matthew P. Reed; Jonathan D. Rupp; Carrie N. Hoff; Jinhuan Zhang; Bo Cheng (Annals of Biomedical Engineering, 2013)

Exploring the diploid wheat ancestral A genome through sequence comparison at the high-molecular-weight glutenin locus region - Lingli Dong; Naxin Huo; Yi Wang; Karin Deal; Ming-Cheng Luo; Daowen Wang; Olin D. Anderson; Yong Qiang Gu (Molecular Genetics and Genomics, 2012)

The Metabolism of Neurons and Astrocytes Through Mathematical Models - E. Somersalo; Y. Cheng; D. Calvetti (Annals of Biomedical Engineering, 2012)

Intracellular-signaling tumor-regression modeling of the pro-apoptotic receptor agonists dulanermin and conatumumab - Brittany P. Kay; Cheng-Pang Hsu; Jian-Feng Lu; Yu-Nien Sun; Shuang Bai; Yan Xin; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

QTLs for murine red blood cell parameters in LG/J and SM/J F2 and advanced intercross lines - Thomas B. Bartnikas; Clarissa C. Parker; Riyan Cheng; Dean R. Campagna; Jackie E. Lim; Abraham A. Palmer; Mark D. Fleming (Mammalian Genome, 2012)

Molecular diversity of bacteria in Yunnan yellow cattle (Bos taurs) from Nujiang region, China - J. Leng; Y. M. Cheng; C. Y. Zhang; R. J. Zhu; S. L. Yang; X. Gou; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2012)

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

Development, Validation, and Application of a Parametric Pediatric Head Finite Element Model for Impact Simulations - Zhigang Li; Jingwen Hu; Matthew P. Reed; Jonathan D. Rupp; Carrie N. Hoff; Jinhuan Zhang; Bo Cheng (Annals of Biomedical Engineering, 2011)

Sensitivity analysis of climatic parameters for sky classification - D. H. W. Li; H. L. Tang; K. L. Cheung; E. W. M. Lee; C. C. K. Cheng (Theoretical and Applied Climatology, 2011)

Fine-mapping alleles for body weight in LG/J × SM/J F2 and F34 advanced intercross lines - Clarissa C. Parker; Riyan Cheng; Greta Sokoloff; Jackie E. Lim; Andrew D. Skol; Mark Abney; Abraham A. Palmer (Mammalian Genome, 2011)

Androgen Receptor Overexpression Is Neuroprotective in Experimental Stroke - Patricia Ayala; Masayoshi Uchida; Kozaburo Akiyoshi; Jian Cheng; Joel Hashimoto; Taiping Jia; Oline K. Ronnekleiv; Stephanie J. Murphy; Kristine M. Wiren; Patricia D. Hurn (Translational Stroke Research, 2011)

EHPC 2010: sharing knowledge on environmental health for risk mitigation - T. E. Ford; A. L. Bass; S. Cheng; G. N. Cherr; B. Cole; E. Fairbairn; J.-D. Gu; R. S. Halbrook; F. E. Löffler; E. L. Madsen; N. A. McGinn (Ecotoxicology, 2011)

A freshwater cyanophage whose genome indicates close relationships to photosynthetic marine cyanomyophages - Theo W. Dreher; Nathan Brown; Connie S. Bozarth; Andrew D. Schwartz; Erin Riscoe; Cameron Thrash; Samuel E. Bennett; Shin‐Cheng Tzeng; Claudia S. Maier (Environmental Microbiology, 2011)
Summary Bacteriophage S‐CRM01 has been isolated from a freshwater strain of Synechococcus and shown to be present in the upper Klamath River valley in northern California and Oregon. The genome of this lytic T4‐like phage has a 178 563 bp circular genetic map with 297 predicted protein‐coding genes and 33 tRNA genes that represent all 20‐amino‐acid specificities. Analyses based on gene sequence and gene content indicate a close phylogenetic relationship to the ‘photosynthetic’ marine cyanomyophages infecting Synechococcus and Prochlorococcus . Such relatedness suggests that freshwater and marine phages can draw on a common gene pool. The genome can be considered as being comprised of three regions. Region 1 is populated predominantly with structural genes, recognized as such by homology to other T4‐like phages and by identification in a proteomic analysis of purified virions. Region 2 contains most of the genes with roles in replication, recombination, nucleotide metabolism and regulation of gene expression, as well as 5 of the 6 signature genes of the photosynthetic cyanomyophages ( hli03 , hsp20 , mazG , phoH and psbA ; cobS is present in Region 3). Much of Regions 1 and 2 are syntenic with marine cyanomyophage genomes, except that a segment encompassing Region 2 is inverted. Region 3 contains a high proportion (85%) of genes that are unique to S‐CRM01, as well as most of the tRNA genes. Regions 1 and 2 contain many predicted late promoters, with a combination of CTAAATA and ATAAATA core sequences. Two predicted genes that are unusual in phage genomes are homologues of cellular spoT and nusG .

Tetherin and Its Viral Antagonists - Björn D. Kuhl; Vicky Cheng; Mark A. Wainberg; Chen Liang (Journal of Neuroimmune Pharmacology, 2011)

Apoptosis to predict copepod mortality: state of the art and future perspectives - I. Buttino; J.-S. Hwang; C.-K. Sun; C.-T. Hsieh; T.-M. Liu; D. Pellegrini; A. Ianora; D. Sartori; G. Romano; S.-H. Cheng; A. Miralto (Hydrobiologia, 2011)

Genomic aspects of research involving polyploid plants - Xiaohan Yang; Chu-Yu Ye; Zong-Ming Cheng; Timothy J. Tschaplinski; Stan D. Wullschleger; Weilun Yin; Xinli Xia; Gerald A. Tuskan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Uranyl Soil Extraction and Fluorescence Enhancement by Nanoporous Silica Gel: pH effects - Chien-Cheng Chen; Dmitry Pestov; Jean D. Nelson; John E. Anderson; Gary Tepper (Journal of Fluorescence, 2011)

Quorum Sensing in Aeromonas Species Isolated from Patients in Malaysia - Kok-Gan Chan; Savithri D. Puthucheary; Xin-Yue Chan; Wai-Fong Yin; Cheng-Siang Wong; Wah-Seng See Too; Kek-Heng Chua (Current Microbiology, 2011)

Expression of GDF-9, BMP-15 and their receptors in mammalian ovary follicles - R. Z. Sun; L. Lei; L. Cheng; Z. F. Jin; S. J. Zu; Z. Y. Shan; Z. D. Wang; J. X. Zhang; Z. H. Liu (Journal of Molecular Histology, 2010)

A multi-modeling approach to evaluating climate and land use change impacts in a Great Lakes River Basin - M. J. Wiley; D. W. Hyndman; B. C. Pijanowski; A. D. Kendall; C. Riseng; E. S. Rutherford; S. T. Cheng; M. L. Carlson; J. A. Tyler; R. J. Stevenson; P. J. Steen; P. L. Richards; et al. (Hydrobiologia, 2010)

Upregulation of coronary endothelial P-selectin in a monkey heart ischemia reperfusion model - Regi Thomas; Yulan Cheng; Jun Yan; Thierry Bettinger; Anne Broillet; Gilles Rioufol; Adrian D. Nunn (Journal of Molecular Histology, 2010)

Assessment of metal contaminations leaching out from recycling plastic bottles upon treatments - Xiaoliang Cheng; Honglan Shi; Craig D. Adams; Yinfa Ma (Environmental Science and Pollution Research, 2010)

Cellular Expression of INK4a Gene in Cells of Bladder Cancer Associated with Human Papilloma Virus-16 - G. M. Volgareva; L. E. Zavalishina; D. A. Golovina; Yu. Yu. Andreeva; V. D. Ermilova; O. B. Trofimova; D. A. Kuevda; O. Yu. Shipulina; V. A. Glazunova; Shuling Cheng; L. S. Pavlova; N. L. Cheban; et al. (Bulletin of Experimental Biology and Medicine, 2010)

Transgenic hybrid aspen overexpressing the Atwbc19 gene encoding an ATP-binding cassette transporter confers resistance to four aminoglycoside antibiotics - Byung-guk Kang; Xia Ye; Lori D. Osburn; C. N. Stewart; Zong-Ming Cheng (Plant Cell Reports, 2010)

Marek’s disease viruses lacking either R-LORF10 or LORF4 have altered virulence in chickens - Taejoong Kim; Henry D. Hunt; Hans H. Cheng (Virus Genes, 2010)

Yersinia ironomics: comparison of iron transporters among Yersinia pestis biotypes and its nearest neighbor, Yersinia pseudotuberculosis - Stanislav Forman; James T. Paulley; Jacqueline D. Fetherston; Yi-Qiang Cheng; Robert D. Perry (BioMetals, 2010)

Atmospheric CO 2 enrichment facilitates cation release from soil - L. Cheng; J. Zhu; G. Chen; X. Zheng; N.‐H. Oh; T. W. Rufty; D. deB. Richter; S. Hu (Ecology Letters, 2010)
Ecology Letters (2010) 13: 284–291 Abstract Atmospheric CO 2 enrichment generally stimulates plant photosynthesis and nutrient uptake, modifying the local and global cycling of bioactive elements. Although nutrient cations affect the long‐term productivity and carbon balance of terrestrial ecosystems, little is known about the effect of CO 2 enrichment on cation availability in soil. In this study, we present evidence for a novel mechanism of CO 2 ‐enhancement of cation release from soil in rice agricultural systems. Elevated CO 2 increased organic C allocation belowground and net H + excretion from roots, and stimulated root and microbial respiration, reducing soil redox potential and increasing Fe 2+ and Mn 2+ in soil solutions. Increased H + , Fe 2+ , and Mn 2+ promoted Ca 2+ and Mg 2+ release from soil cation exchange sites. These results indicate that over the short term, elevated CO 2 may stimulate cation release from soil and enhance plant growth. Over the long‐term, however, CO 2 ‐induced cation release may facilitate cation losses and soil acidification, negatively feeding back to the productivity of terrestrial ecosystems.

Phylogenetic analysis of 16S rRNA gene sequences reveals rumen bacterial diversity in Yaks (Bos grunniens) - L. Y. Yang; J. Chen; X. L. Cheng; D. M. Xi; S. L. Yang; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2010)

Phenotypic divergence during the invasion of Phyla canescens in Australia and France: evidence for selection‐driven evolution - Cheng‐Yuan Xu; Mic H. Julien; Mohammad Fatemi; Christophe Girod; Rieks D. Van Klinken; Caroline L. Gross; Stephen J. Novak (Ecology Letters, 2010)
Rapid adaptive evolution has been advocated as a mechanism that promotes invasion. Demonstrating adaptive evolution in invasive species requires rigorous analysis of phenotypic shifts driven by selection. Here, we document selection‐driven evolution of Phyla canescens , an Argentine weed, in two invaded regions (Australia and France). Invasive populations possessed similar or higher diversity than native populations, and displayed mixed lineages from different sources, suggesting that genetic bottlenecks in both countries might have been alleviated by multiple introductions. Compared to native populations, Australian populations displayed more investment in sexual reproduction, whereas French populations possessed enhanced vegetative reproduction and growth. We partitioned evolutionary forces (selection vs. stochastic events) using two independent methods. Results of both analyses suggest that the pattern of molecular and phenotypic variability among regions was consistent with selection‐driven evolution, rather than stochastic events. Our findings indicate that selection has shaped the evolution of P . canescens in two different invaded regions. Ecology Letters (2010) 13: 32–44

Environmental biological model based on optimization of activated sludge process - X. X. Zhang; D. Y. Zhao; Z. X. Wang; B. Wu; W. X. Li; S. P. Cheng (International Journal of Environmental Science and Technology, 2009)

Salicylic acid stimulates secretion of the normally symplastic enzyme mannitol dehydrogenase: a possible defense against mannitol-secreting fungal pathogens - Fang-yi Cheng; Eli Zamski; Wei-wen Guo; D. Mason Pharr; John D. Williamson (Planta, 2009)

Drepanocladus longifolius (Amblystegiaceae), an addition to the moss flora of King George Island, South Shetland Islands, with a review of Antarctic benthic mosses - Su-Ping Li; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Ming-Hong Cai; Hai-Ying Wang; Cheng-Sen Li (Polar Biology, 2009)

First Molecular Detection of Group A Rotaviruses in Drinking Water Sources in Beijing, China - X. Q. He; L. Cheng; D. Y. Zhang; W. Li; X. M. Xie; M. Ma; Z. J. Wang (Bulletin of Environmental Contamination and Toxicology, 2009)

Identification of the flavin-dependent monooxygenase-encoding YUCCA gene family in Populus trichocarpa and their expression in vegetative tissues and in response to hormone and environmental stresses - Xia Ye; Byung-guk Kang; Lori D. Osburn; Yi Li; Cheng Zong-Ming (Max) (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Structural characterization of Brachypodium genome and its syntenic relationship with rice and wheat - Naxin Huo; John P. Vogel; Gerard R. Lazo; Frank M. You; Yaqin Ma; Stephanie McMahon; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Plant Molecular Biology, 2009)

Biomechanics: Cell Research and Applications for the Next Decade - Dennis Discher; Cheng Dong; Jeffrey J. Fredberg; Farshid Guilak; Donald Ingber; Paul Janmey; Roger D. Kamm; Geert W. Schmid-Schönbein; Sheldon Weinbaum (Annals of Biomedical Engineering, 2009)

Preliminary Risk Assessment of Trace Metal Pollution in Surface Water from Yangtze River in Nanjing Section, China - B. Wu; D. Y. Zhao; H. Y. Jia; Y. Zhang; X. X. Zhang; S. P. Cheng (Bulletin of Environmental Contamination and Toxicology, 2009)

Preliminary Risk Assessment of Trace Metal Pollution in Surface Water from Yangtze River in Nanjing Section, China - B. Wu; D. Y. Zhao; H. Y. Jia; Y. Zhang; X. X. Zhang; S. P. Cheng (Bulletin of Environmental Contamination and Toxicology, 2009)

High-resolution Mapping of In Vivo Gastrointestinal Slow Wave Activity Using Flexible Printed Circuit Board Electrodes: Methodology and Validation - Peng Du; G. O’Grady; J. U. Egbuji; W. J. Lammers; D. Budgett; P. Nielsen; J. A. Windsor; A. J. Pullan; L. K. Cheng (Annals of Biomedical Engineering, 2009)

Nicotine is a Selective Pharmacological Chaperone of Acetylcholine Receptor Number and Stoichiometry. Implications for Drug Discovery - Henry A. Lester; Cheng Xiao; Rahul Srinivasan; Cagdas D. Son; Julie Miwa; Rigo Pantoja; Matthew R. Banghart; Dennis A. Dougherty; Alison M. Goate; Jen C. Wang (The AAPS Journal, 2009)

A comparison of fine root distribution and water consumption of mature Caragana korshinkii Kom grown in two soils in a semiarid region, China - Xiangrong Cheng; Mingbin Huang; Mingan Shao; D. N. Warrington (Plant and Soil, 2009)

Ligand-induced nuclear translocation of S1P1 receptors mediates Cyr61 and CTGF transcription in endothelial cells - Rosendo Estrada; Lichun Wang; Venkatakrishna R. Jala; Jen-Fu Lee; Cheng-Yon Lin; Robert D. Gray; Bodduluri Haribabu; Menq-Jer Lee (Histochemistry and Cell Biology, 2009)

High levels of genetic variation at MHC class II DBB loci in the tammar wallaby (Macropus eugenii) - Yuanyuan Cheng; Hannah V. Siddle; Stephan Beck; Mark D. B. Eldridge; Katherine Belov (Immunogenetics, 2009)

Peginterferon vs. interferon in the treatment of different HCV genotype infections in HIV patients - S. Zhao; D. Cheng; E. Liu; H. Yu; H. Yang; X. Xue; Y. Chu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Organochlorine Pesticides in the Soil in Linfen, China - H. X. Cheng; S. Fu; Y. H. Liu; D. S. Li; J. H. Zhou; X. J. Xia (Bulletin of Environmental Contamination and Toxicology, 2008)

Virulent Hessian Fly Larvae Manipulate the Free Amino Acid Content of Host Wheat Plants - Kurt D. Saltzmann; Marcelo P. Giovanini; Cheng Zheng; Christie E. Williams (Journal of Chemical Ecology, 2008)

Characterization of apoptosis induced by grouper iridovirus in two newly established cell lines from barramundi, Lates calcarifer (Bloch) - Y‐S Lai; P P Chiou; W‐J Chen; Y‐C Chen; C‐W Chen; I‐S Chiu; S‐D Chen; Y‐H Cheng; C‐Y Chang (Journal of Fish Diseases, 2008)
Two new cell lines have been established from the muscle and swim bladder tissues of barramundi, Lates calcarifer , and designated as BM (barramundi muscle) and BSB (barramundi swimbladder), respectively. The cells multiplied well at 28 °C in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum, and have been continuously subcultured more than 100 times to date. Morphologically, BM cells were mostly fibroblastic, whereas BSB were mostly epithelial. Both cell lines were susceptible to grouper iridovirus (GIV) and displayed characteristics of apoptosis after viral infection. The induction of apoptosis was further assayed in GIV‐infected BM and BSB cells by various methods. The inhibition of cell growth by GIV was demonstrated by MTT [3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide] assay. Morphological observations revealed typical apoptotic features in the infected cells, including cell shrinkage and rounding, chromosome condensation and formation of apoptotic body‐like vesicles. Chromosome fragmentation was detected by DNA laddering and TUNEL assays. Finally, the appearance of phosphotidylserine on the outer leaflet of apoptotic cell membranes was confirmed by annexin V staining. This is the first report of apoptosis induced by GIV in fish cells.

New and rare lignicolous hyphomycetes from Zhejiang Province, China - Mongkol Wongsawas; Hong-kai Wang; Kevin D. Hyde; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Fungal diversity on fallen leaves of Ficus in northern Thailand - Hong-kai Wang; Kevin D. Hyde; Kasem Soytong; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Antioxidative activities and the total phenolic contents of tonic Chinese Medicinal Herbs - D.-J. Guo; H.-L. Cheng; S.-W. Chan; P. H.-F. Yu (Inflammopharmacology, 2008)

Ecology of urban lawns under three common management programs - Z. Cheng; D. S. Richmond; S. O. Salminen; P. S. Grewal (Urban Ecosystems, 2008)

The nuclear genome of Brachypodium distachyon: analysis of BAC end sequences - Naxin Huo; Gerard R. Lazo; John P. Vogel; Frank M. You; Yaqin Ma; Daniel M. Hayden; Devin Coleman-Derr; Theresa A. Hill; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Functional & Integrative Genomics, 2008)

Optimal Water Resource Allocation in Arid and Semi-Arid Areas - Jin F. Wang; Guo D. Cheng; Yi G. Gao; Ai H. Long; Zhong M. Xu; Xin Li; Hongyan Chen; Tom Barker (Water Resources Management, 2008)

Detecting infestation of take‐all disease in wheat using Landsat Thematic Mapper imagery - X. Chen; J. Ma; H. Qiao; D. Cheng; Y. Xu; Y. Zhao (International Journal of Remote Sensing, 2007)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Genetic diversity of cowpea [Vigna unguiculata (L.) Walp.] in four West African and USA breeding programs as determined by AFLP analysis - Jinggui Fang; Chih-Cheng T. Chao; Philip A. Roberts; Jeffrey D. Ehlers (Genetic Resources and Crop Evolution, 2007)

Commentary on AAPS Workshop - Cheng Tong; Susan S. D’Souza; Jan E. Parker; Tahseen Mirza (Pharmaceutical Research, 2007)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Urinary levels of RANTES and M-CSF are predictors of lupus nephritis flare - S. Tian; J. Li; L. Wang; T. Liu; H. Liu; G. Cheng; D. Liu; Y. Deng; R. Gou; Y. Wan; J. Jia; C. Chen (Inflammation Research, 2007)

Application of LIDAR Technique and MM5-CMAQ Modeling Approach for the Assessment of Winter PM10 Air Pollution: A Case Study in Beijing, China - D. S. Chen; S. Y. Cheng; J. B. Li; T. Chen; X. Y. Zhao; X. R. Guo; H. L. Hu; T. Yu (Water, Air, & Soil Pollution, 2007)

Electro-mechanical stability of surface EMG sensors - S. H. Roy; G. De Luca; M. S. Cheng; A. Johansson; L. D. Gilmore; C. J. De Luca (Medical & Biological Engineering & Computing, 2007)

Fine mapping of the Pc locus of Sorghum bicolor, a gene controlling the reaction to a fungal pathogen and its host-selective toxin - Ervin D. Nagy; Tso-Ching Lee; Wusirika Ramakrishna; Zijun Xu; Patricia E. Klein; Phillip SanMiguel; Chiu-Ping Cheng; Jingling Li; Katrien M. Devos; Keith Schertz; Larry Dunkle; Jeffrey L. Bennetzen (Theoretical and Applied Genetics, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Analysis of candidate genes on chromosome 2 in oral cleft case-parent trios from three populations - T. H. Beaty; J. B. Hetmanski; M. D. Fallin; J. W. Park; J. W. Sull; I. McIntosh; K. Y. Liang; C. A. VanderKolk; R. J. Redett; S. A. Boyadjiev; E. W. Jabs; S. S. Chong; et al. (Human Genetics, 2006)

The 73 kD Subunit of the cleavage and polyadenylation specificity factor (CPSF) complex affects reproductive development in Arabidopsis - Ruqiang Xu; Hongwei Zhao; Randy D. Dinkins; Xiaowen Cheng; George Carberry; Qingshun Quinn Li (Plant Molecular Biology, 2006)

Prenatal alcohol exposure (PAE) reduces the size of the forepaw representation in forepaw barrel subfield (FBS) cortex in neonatal rats: relationship between periphery and central representation - Cecilia P. Margret; Tyson D. Chappell; Cheng X. Li; Taha A. Jan; Shannon G. Matta; Andrea J. Elberger; Robert S. Waters (Experimental Brain Research, 2006)

Variations in Indoor PM10 Concentrations in Sixteen Homes in Guiyang City, People's Republic of China - Y. L. Cheng; M. Yan; J. L. Li; Z. R. Liu; Y. H. Bai; W. Tian; D. G. Wu; Q. Cheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Prenatal alcohol exposure delays the development of the cortical barrel field in neonatal rats - Cecilia P. Margret; Cheng X. Li; Tyson D. Chappell; Andrea J. Elberger; Shannon G. Matta; Robert S. Waters (Experimental Brain Research, 2006)

Estimating the underwater light field from remote sensing of ocean color - Cheng-Chien Liu; Richard L. Miller; Kendall L. Carder; Zhongping Lee; Eurico J. D’Sa; James E. Ivey (Journal of Oceanography, 2006)

Organochlorine Pesticides in Tissues of Catfish (Silurus asotus) from Guanting Reservoir, People's Republic of China - D. X. Cheng; Z. Z. Yang; X. T. Wang; Y. Z. Sun; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2006)

Single-Column Model Intercomparison for a Stably Stratified Atmospheric Boundary Layer - J. Cuxart; A. A. M. Holtslag; R. J. Beare; E. Bazile; A. Beljaars; A. Cheng; L. Conangla; M. Ek; F. Freedman; R. Hamdi; A. Kerstein; H. Kitagawa; et al. (Boundary-Layer Meteorology, 2006)

Solubility and Stability of Calcium Arsenates at 25∘C - Y. N. Zhu; X. H. Zhang; Q. L. Xie; D. Q. Wang; G. W. Cheng (Water, Air, & Soil Pollution, 2006)

A catalog of nonsynonymous polymorphism on mouse Chromosome 16 - Jeffrey M. Kidd; Karrie C. Trevarthen; David L. Tefft; Ze Cheng; Michaele Mooney; Mark D. Adams (Mammalian Genome, 2005)

GGM02 – An improved Earth gravity field model from GRACE - B. Tapley; J. Ries; S. Bettadpur; D. Chambers; M. Cheng; F. Condi; B. Gunter; Z. Kang; P. Nagel; R. Pastor; T. Pekker; S. Poole; et al. (Journal of Geodesy, 2005)

Transforming growth factor-β1 regulation of laminin γ1 and fibronectin expression and survival of mouse mesangial cells - Yan Jiang; Davis W. Cheng; Errol D. Crook; Lalit P. Singh (Molecular and Cellular Biochemistry, 2005)

Prenatal alcohol exposure alters the size, but not the pattern, of the whisker representation in neonatal rat barrel cortex - Cecilia P. Margret; Cheng X. Li; Andrea J. Elberger; Shannon G. Matta; Tyson D. Chappell; Robert S. Waters (Experimental Brain Research, 2005)

Optimal and sustainable extraction of groundwater in coastal aquifers - Khalid Qahman; Abdelkader Larabi; Driss Ouazar; Ahmed Naji; Alexander H. -D. Cheng (Stochastic Environmental Research and Risk Assessment, 2005)

In Vitro and Pharmacophore-Based Discovery of Novel hPEPT1 Inhibitors - Sean Ekins; Jeffrey S. Johnston; Praveen Bahadduri; Vanessa M. D’Souza; Abhijit Ray; Cheng Chang; Peter W. Swaan (Pharmaceutical Research, 2005)

Antisense inhibition of sorbitol synthesis leads to up-regulation of starch synthesis without altering CO2 assimilation in apple leaves - Lailiang Cheng; Rui Zhou; Edwin J. Reidel; Thomas D. Sharkey; Abhaya M. Dandekar (Planta, 2005)

Voltammetric studies of Zn and Fe complexes of EDTA: Evidence for the push mechanism - Ryan M. Hutcheson; Mark D. Engelmann; I. Francis Cheng (BioMetals, 2005)

Functional and regulatory analysis of the Arabidopsis thaliana CAX2 cation transporter - Jon K. Pittman; Toshiro Shigaki; Joy L. Marshall; Jay L. Morris; Ning-Hui Cheng; Kendal D. Hirschi (Plant Molecular Biology, 2004)

Effects of Azinphos-Methyl on Cholinergic Responses and General Health in Zebra Finches (Taeniopygia guttata) After Previous Treatment with p,p′-DDE - H Gill; T D Williams; C A Bishop; K M Cheng; J E Elliott (Archives of Environmental Contamination and Toxicology, 2004)

A hypothesis for the basis of the pro-oxidant nature of calcium ions - Ryan Hutcheson; Mark D. Engelmann; I. Francis Cheng (BioMetals, 2004)

Climate and Productivity of Major Conifer Species in the Interior of British Columbia, Canada - Gordon D. Nigh; Cheng C. Ying; Hong Qian (Forest Science, 2004)
Lodgepole pine (Pinus contorta var. latifolia Engelm. ex S. Wats.), interior spruce (including Picea glauca (Moench) Voss, P. engelmannii Parry ex. Engelm., P. glauca×engelmannii), and interior Douglas-fir (Pseudotsuga menziesiivar. glauca (Beissn.) Franco) are the most important commercial species in the interior of British Columbia. We develop statistical models to predict site index (a measure of site productivity) from climate for these species. Using data from 193 climate stations, we first developedmodels that predict mean annual temperature, mean temperature of the warmest and coldest months, number of frost-free days, and frost-free period from latitude, longitude, and elevation. With these models and the Parameter-elevation Regressions on Independent Slopes Model (used to predictmean annual and mean summer precipitation), we predict 10 climate attributes for site index plots of lodgepole pine, interior spruce, and interior Douglas-fir. These attributes are then used in regression models to estimate site index. The models allow us to investigate the current relationshipbetween climate (particularly temperature and precipitation) and site productivity for these species. The productivity for all the species studied increased as temperature increased, with lodgepole pine exhibiting the greatest response. The productivity of lodgepole pine and interior Douglas-firalso increased with increasing precipitation, with interior Douglas-fir having a greater response than lodgepole pine. We discuss the application of the models in relation to the impact of climate change on site productivity. FOR. SCI. 50(5):659–671.

Economic Analyses of Sequestering Carbon in Loblolly Pine, Cherrybark Oak, and Northern Red Oak in the United States - Ching-Hsun Huang; Richard Bates; Gary D. Kronrad; Shiaolin Cheng (Environmental Management, 2004)

Targeted cybridization in citrus: transfer of Satsuma cytoplasm to seedy cultivars for potential seedlessness - D. Prasad; Y. J. Cheng; P. Serrano; X. X. Deng; J. W. Grosser; W. W. Guo (Plant Cell Reports, 2004)

Variability of the Fenton reaction characteristics of the EDTA, DTPA, and citrate complexes of iron - Mark D. Engelmann; Robert T. Bobier; Terrance Hiatt; I. Francis Cheng (BioMetals, 2003)

Augmented responses to morphine and cocaine in mice with a 12-lipoxygenase gene disruption - Carrie L. Walters; Bao-Cheng Wang; Misty Godfrey; Duxin Sun; Colin D. Funk; Julie A. Blendy (Psychopharmacology, 2003)

Structural Determinants of P-Glycoprotein-Mediated Transport of Glucocorticoids - Charles R. Yates; Cheng Chang; Jeffrey D. Kearbey; Kazuto Yasuda; Erin G. Schuetz; Duane D. Miller; James T. Dalton; Peter W. Swaan (Pharmaceutical Research, 2003)

Genomic characterization of Rim2 / Hipa elements reveals a CACTA-like transposon superfamily with unique features in the rice genome - G.-D. Wang; P.-F. Tian; Z.-K. Cheng; G. Wu; J.-M. Jiang; D.-B. Li; Q. Li; Z.-H. He (Molecular Genetics and Genomics, 2003)

Delayed reorganization of the shoulder representation in forepaw barrel subfield (FBS) in first somatosensory cortex (SI) following forelimb deafferentation in adult rats - Phillip P. Pearson; Cheng X. Li; Tyson D. Chappell; Robert S. Waters (Experimental Brain Research, 2003)

Surprisingly minor influence of TRAV11 (Vα14) polymorphism on NK T-receptor mCD1/α-galactosylceramide binding kinetics - Bee-Cheng Sim; Kaisa Holmberg; Stephane Sidobre; Olga Naidenko; Nathalie Niederberger; Shane D. Marine; Mitchell Kronenberg; Nicholas R. J. Gascoigne (Immunogenetics, 2003)

Characterization and Temporal Variation of Asian Dust Aerosol from a Site in the Northern Chinese Deserts - X. Y. Zhang; S. L. Gong; R. Arimoto; Z. X. Shen; F. M. Mei; D. Wang; Y. Cheng (Journal of Atmospheric Chemistry, 2003)

Brevetoxin Concentrations in Marine Aerosol: Human Exposure Levels During a Karenia brevis Harmful Algal Bloom - R. H. Pierce; M. S. Henry; P. C. Blum; J. Lyons; Y. S. Cheng; D. Yazzie; Y. Zhou (Bulletin of Environmental Contamination and Toxicology, 2003)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Differential distribution of interneurons in the neural networks that control walking in the mudpuppy (Necturus maculatus) spinal cord - J. Cheng; K. Jovanovic; Y. Aoyagi; D. J. Bennett; Y. Han; R. B. Stein (Experimental Brain Research, 2002)

Macrolide Resistance and Distribution of erm and mef Genes Among Beta-Haemolytic Streptococci in Hong Kong - M. Ip; D. Lyon; T. Leung; A. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Distinctive KIR and HLA diversity in a panel of north Indian Hindus - Raja Rajalingam; Peter Krausa; Heather G. Shilling; Jason B. Stein; Arumugam Balamurugan; Malcolm D. McGinnis; Nathalie W. Cheng; Narinder K. Mehra; Peter Parham (Immunogenetics, 2002)

Expression of afibrobacter succinogenes 1,3-1,4-β-glucanase in Potato (Solanum tuberosum) - John D. Armstrong; G. Douglas Inglis; Lawrence M. Kawchuk; Tim A. McAllister; Fran Leggett; Dermot R. Lynch; L. Brent Selinger; K. J. Cheng (American Journal of Potato Research, 2002)

Temporal and spatial expression patterns of TUB9, a β-tubulin gene of Arabidopsis thaliana - Zigang Cheng; D. Peter Snustad; John V. Carter (Plant Molecular Biology, 2001)

Noninvasive Electrical Imaging of the Heart: Theory and Model Development - A. J. Pullan; L. K. Cheng; M. P. Nash; C. P. Bradley; D. J. Paterson (Annals of Biomedical Engineering, 2001)

Corrosion Properties of Nanocrystalline Co–Cr Coatings - D. Cheng; V. L. Tellkamp; C. J. Lavernia; E. J. Lavernia (Annals of Biomedical Engineering, 2001)

Special Issue of Transport in Porous Media on ‘Seawater Intrusion in Coastal Aquifers’ - Alexander H.-D. Cheng; Leonard F. Konikow; Driss Ouazar (Transport in Porous Media, 2001)

Effects of [CO2] and nitrogen fertilization on soils planted with ponderosa pine - D. W. Johnson; W. Cheng; J. T. Ball (Plant and Soil, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Removal of cardiac beat artifact in oesophageal pressure measurement by frequency analysis - Y. P. Cheng; H. D. Wu; C. Y. Wang; G. J. Jan (Medical & Biological Engineering & Computing, 1999)

Robust estimation of systematic errors of satellite laser range - Y. Yang; M. K. Cheng; C. K. Shum; B. D. Tapley (Journal of Geodesy, 1999)

Isotopic constraints on the Easter Seamount Chain source - Q. C. Cheng; J. D. Macdougall; P. Zhu (Contributions to Mineralogy and Petrology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Expression of neurotrophins, GDNF, and their receptors in rat thyroid tissue - N. Belluardo; G. Mudò; G. Caniglia; M. Corsaro; Q. Cheng; F. Frasca; A. Belfiore; D. F. Condorelli (Cell and Tissue Research, 1999)

Genetic Evaluation of a Demographic Bottleneck in the Greater Prairie Chicken - Juan L. Bouzat; Hans H. Cheng; Harris A. Lewin; Ronald L. Westemeier; Jeffrey D. Brawn; Ken N. Paige (Conservation Biology, 1998)

Genetic Evaluation of a Demographic Bottleneck in the Greater Prairie Chicken - Juan L. Bouzat; Hans H. Cheng; Harris A. Lewin; Ronald L. Westemeier; Jeffrey D. Brawn; Ken N. Paige (Conservation Biology, 1998)
Although the theoretical relationship between population size, fitness, and genetic variation is well established, only a few studies have provided direct evidence that ties a decline in both genetic variation and fitness to a demographic bottleneck for a natural system. We report on a genetic comparison of four populations of the Greater Prairie Chicken ( Tympanuchus cupido ) with different demographic histories. Specifically, we compared a population from Illinois that has suffered an extreme demographic contraction and an associated decline in population fitness (measured in terms of hatchability rates) with populations from Kansas, Nebraska, and Minnesota with no known history of bottlenecks or associated declines in fitness. Using the polymerase chain reaction, we amplified six microsatellite loci from which levels of heterozygosity, allelic diversity, and geographic differentiation ( F ST and R ST ) of the studied populations were estimated. Results of this analysis showed that the Illinois Prairie Chicken had the lowest estimate of mean heterozygosity per locus and approximately two‐thirds the allelic diversity, sharing 95–100% of all their alleles with each of the other populations. This finding suggests that the Illinois Prairie Chicken originally had higher levels of genetic diversity that were subsequently lost through an extreme demographic contraction. To our knowledge this is the first example of loss of genetic diversity being associated with a decrease in population fitness as a result of a known demographic bottleneck in a wild bird species. Evaluación Genética de un Cuello de Botella Demográfico en la Gran Gallineta de la Pradera Aunque la relación teórica entre el tamaño poblacional, la aptitud biológica y la variabilidad genética ha sido bien establecida, son pocos lo astudios que han proporcionado evidencia directa que asocie una disminución de la variación genética y de la aptitud biológica con un cuello de botella demografico en sistemas naturales. Reportamos una comparación genética de cuatro poblaciones de la gran gallineta de la pradera ( Tympanucus cupido ) que tuvieron historias demográficas diferentes. Específicamente comparamos una población de Illinois, la cual ha sufrido una contracción demográfica extrema asociada con decrementos en la aptitud biológica poblacional (medida en términos de tasas de eclosión), con poblaciones de Kansas, Nebraska y Minnesota, las cuales no presentan una historia de cuello de botella poblacional ni decrementos en la aptitud bioloógica. Mediante el uso de la reacción en cadena de la polimerasa (PCR) amplificamos seis marcadores de microsatélites con los cuales estimamos niveles de heterocigósis, diversidad alélica y diferenciación geográfica ( F ST y R ST ) en las poblaciones estudiadas. La gran gallineta de la pradera en Illinois presenta el menor valor de heterocigosidad promedio por locus y aproximademente 2/3 de la diversidad alélica, compartiendo 95–100% de sus alelos con cada una de las otras poblaciones. Estos resultados sugieren que la población de Illinois presentaba originalmente niveles mayores de variabilidad genética, los cuales fueron perdidos consecuentemente a través de un contracción demográfica extrema. A nuestro entender, este estudio representa el primer ejemplo en el que se asocia la pérdida de la diversidad genética en una especie de ave silvestre con la disminución en la aptitud poblacional y como resultado de un cuello de botella demográfico conocido.

Abundance of mRNAs encoding HMG1/HMG2 class high-mobility-group DNA-binding proteins are differentially regulated in cotyledons of Pharbitis nil - Sharman D. O'Neill; Cheng Chao Zheng (Plant Molecular Biology, 1998)

Comparison of E-test with agar dilution for determining susceptibility ofStreptococcus pneumoniae to penicillin - O. Scheel; D. J. Lyon; D. N. C. Tsang; A. F. B. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Aluminum Toxicity and Nutrient Utilization in the Mycorrhizal Fungus Hebeloma mesophacus - F.-X. Kong; Y. Liu; F.-D. Cheng (Bulletin of Environmental Contamination and Toxicology, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

American Elm: Building in Resistance to Dutch Elm Disease - Z.-M. Cheng; N.-Q. Shi; D. E. Herman; T. K. Capps (Journal of Forestry, 1997)

Plant regeneration from leaf tissues of four North Dakota genotypes of potato (Solanum tuberosum L.) - Y. D. Park; D. H. Ronis; A. A. Boe; Z. M. Cheng (American Journal of Potato Research, 1995)

Commodity program flexibility and U.S. potato acreage - Hsiang-Tai Cheng; Michele C. Marra; James D. Leiby (American Journal of Potato Research, 1992)

Co-expression of hepatitis B virus antigens by a non-defective adenovirus vaccine vector - Wei Wei Ye; B. B. Mason; Murty Chengalvala; Sheau-Mei Cheng; G. Zandle; M. D. Lubeck; Shaw-Guang Lee; Satoshi Mizutani; A. R. Davis; P. P. Hung (Archives of Virology, 1991)

Factors affecting consumer purchase decision for round white potatoes - H. Cheng; A. S. Kezis; S. R. Peavey; D. A. Smith (American Journal of Potato Research, 1990)

Developmental toxicity of Guthion in rats and mice - Robert D. Short; Jan L. Minor; Cheng-Chun Lee; Neil Chernoff; Ronald L. Baron (Archives of Toxicology, 1980)